Study of Central Exclusive Production of π+π−, K+K− and pairs in proton-proton collisions at GeV with the STAR detector at RHIC - STAR Collaboration (Journal of High Energy Physics, 2026)
A bstract We report on the first measurement of the Central Exclusive Production process in proton-proton collisions: pp → ph + h − p (where h = π , K , p ) at the center-of-mass energy $$\sqrt{s}=510$$ GeV with the STAR experiment at RHIC. At this energy, the process is dominated by a double Pomeron exchange mechanism. Hence, it provides a clean environment for investigating Pomeron interactions by measuring fully reconstructed final states involving only two hadrons and two forward scattered protons. The oppositely charged hadron pairs are measured within the central detector of STAR. The forward scattered protons are measured in the Roman Pot system allowing the verification of the event’s exclusivity. Differential fiducial cross sections within the STAR acceptance are presented as a function of the difference in the azimuthal angle between the outgoing protons. The invariant masses of the charged hadron pairs are measured up to approximately 3 GeV and the square of the four-momentum transfer ( t 1 and t 2 ) of the two forward-scattered protons in the range 0.3 GeV 2 < − t 1 , − t 2 < 1.6 GeV 2 . The differential fiducial cross sections of the forward protons as a function of the | t 1 + t 2 | are also presented. All results for the π + π − pair are presented in three mass ranges. A comparison with GRANIITTI Monte Carlo predictions are also presented, where the spectra include continuum and resonant contributions. The observed spectra are consistent with double Pomeron exchange, including resonances seen in previous studies.
Keywords: dept.phy

Measurement of inclusive J/ψ production in Au+Au collisions at sNN=54.4 GeV at STAR - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2026)
This article presents measurements of inclusive J / ψ production at midrapidity (| y | < 1.0) in Au+Au collisions at sNN=54.4 GeV with the STAR detector at the Relativistic Heavy Ion Collider. A suppression of the J / ψ yield, quantified using the nuclear modification factors ( R AA, R CP), is observed with respect to the scaled production in p+p collisions. The dependence of R AA on collision centrality and J / ψ transverse momentum is measured with improved precision compared to previous measurements at 39 and 62.4 GeV, while the centrality dependence of R CP is measured and compared to the same results at 39, 62.4, and 200 GeV. In central collisions, no significant collision energy dependence of R AA is found within uncertainties for collision energies between 17.3 and 200 GeV. Two transport model calculations that include dissociation and regeneration contributions are consistent with the experimental results within uncertainties. Although no significant collision energy dependence of the J / ψ suppression in high energy heavy-ion collisions up to sNN=200 GeV is observed within uncertainties, the newly measured results at 54.4 GeV Au+Au collisions provide additional constraints on theoretical calculations of the hot medium evolution and cold nuclear matter effects. © 2026 The Authors.
Keywords: Nuclear modification factor; Quark-gluon plasma; Quarkonium; dept.phy

Evidence of Spin-Interference Effects in Exclusive 𝐽/𝜓 → 𝑒+⁢𝑒− Photoproduction in Ultraperipheral Heavy-Ion Collisions - STAR Collaboration (Physical Review Letters, 2026)
Here, we report the first evidence of spin interference in exclusive 𝐽/𝜓 → 𝑒+⁢𝑒− photoproduction in ultraperipheral heavy-ion collisions at STAR at $\sqrt{𝑠_{𝑁⁢𝑁}}$ = 200 GeV. In Au + Au collisions, a negative cos⁡(2⁢𝜙) modulation is found for 𝑝𝑇 < 120 MeV/𝑐 with a significance of 3.2⁢𝜎, while the isobar data (Ru + Ru, Zr + Zr) show a consistent negative modulation with a significance of 1.9⁢𝜎, opposite in sign to that in 𝜌0 → 𝜋+⁢𝜋− photoproduction. This establishes for the first time that the interference sign is controlled by the spin structure of the final-state daughters, resolving the ambiguity present in the all-boson 𝜌0 channel. The compact 𝐽/𝜓 probes gluon distributions at perturbative scales, resulting in a weaker modulation and providing stringent constraints on color glass condensate calculations. These findings demonstrate that spin-dependent interference in heavy vector mesons provides a new, experimentally accessible handle on gluon structure beyond traditional cross-section measurements.
Keywords: dept.phy

Measurement of transverse polarization of Λ and hyperons inside jets in unpolarized proton-proton collisions at GeV - STAR Collaboration (Journal of High Energy Physics, 2026)
A surprisingly large transverse polarization of Λ hyperons in unpolarized hadron-nucleon/nucleus collisions has been observed for 50 years, and the origin of this polarization remains an important open question. Recently, theoretical frameworks have advanced in describing this puzzle with the polarizing fragmentation function (PFF). We report the first measurement of Λ and transverse polarization inside jets in unpolarized proton-proton collisions, which is directly attributed to the PFF. The polarization is measured as a function of the jet transverse momentum, the fraction of the jet momentum carried by hyperons, and the transverse momentum of hyperons relative to the jet axis. Covering a wide jet-energy range, these data provide the first constraints on the gluon PFF and allow tests of TMD evolution and its universality. © The Author(s) 2026.
Keywords: Hadron-Hadron Scattering; Jets; Polarization; Proton-Proton Scattering; dept.phy

Measurement of fifth- and sixth-order fluctuations of (net-)proton number in Au + Au collisions from phase II of the beam energy scan program at RHIC - STAR Collaboration (Physical review. C, 2026)
Keywords: Beam (structure); Beam energy; Energy (signal processing); Measure (data warehouse); Phase (matter); dept.phy

Identified charged hadron production in Au + Au collisions at s N N = 54.4 GeV with the STAR detector - STAR Collaboration (Physical review. C, 2026)
We present results on the production of $π^{±}$, $K^{±}$, $p$, and $\bar{p}$ in Au+Au collisions at $\sqrt{s_NN}$ = 54.4~GeV using the STAR detector at RHIC, at midrapidity ($|y| <$ 0.1). Invariant yields of these particles as a function of transverse momentum are shown. We determine bulk properties such as integrated particle yields ($dN/dy$), mean transverse momentum ($\langle p_{T} \rangle$), particle ratios, which provide insight into the particle production mechanisms. Additionally, the kinetic freezeout parameters ($T_\text{kin}$ and $\langle β_{T} \rangle$), which provide information about the dynamics of the system at the time of freezeout, are obtained. The Bjorken energy density ($ε_{\rm{BJ}}$), which gives an estimate of the energy density in the central rapidity region of the collision zone at the formation time $τ$, is calculated and presented as a function of multiplicity for various energies. The results are compared with those from the models such as A Multi-Phase Transport (AMPT) and Heavy Ion Jet INteraction Generator (HIJING) for further insights.
Keywords: Detector; Hadron; Large Hadron Collider; Production (economics); Star (game theory)

The solar neighborhood LIV: 54 orbits of M dwarf multiples within 30 pc with speckle interferometry at SOAR - Vrijmoet, Eliot; Tokovinin, Andrei; Henry, Todd; Winters, Jennifer; Jao, Wei‐Chun; Horch, Elliott (The Astronomical Journal, 2026)
Abstract We present 1066 speckle measurements of M dwarf multiples observed over 2021–2024, all taken with HRCam on the Southern Astrophysical Research 4.1 m telescope. Among these, 900 observations resolve companions in 212 pairs, with separations spanning 17 mas to 3 . ″ 4 and brightness differences ranging from 0 to 4.9 mag in the I filter. We have characterized the orbits of 54 of these companions, spanning periods of 0.67–30 yr, by combining our data with literature astrometry, radial velocities, and, in four cases, Hipparcos–Gaia accelerations. Among the orbits presented here are 28 that are the first-ever such characterizations for their systems and 26 that revise previously published orbits, thus providing a significant update to the observed dynamics of M dwarfs in the solar neighborhood. From these orbits, we provide new and updated dynamical total masses for these systems, precise to 0.7%–7% in nearly all cases. Future mass derivations for components in these systems will contribute to efforts in refining the mass–luminosity relation for the smallest stars and will enhance investigations of age, magnetism, and metallicity effects on luminosities at a given mass.
Keywords: Brightness; Interferometry; Metallicity; Radial velocity; Solar System; Speckle imaging; Speckle pattern; Stars; dept.phy

Nanoelectronics, nanophotonics, and quantum technologies - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, Haifeng (Selected topics in electornics and systems, 2025)
Keywords: Field (mathematics); Quantum; Quantum computer; Quantum dot; Quantum entanglement; Quantum technology; dept.phy

Measuring spin correlation between quarks during QCD confinement - STAR Collaboration (Nature, 2026)
The vacuum is now understood to have a rich and complex structure, characterized by fluctuating energy fields1 and a condensate of virtual quark-antiquark pairs. The spontaneous breaking of the approximate chiral symmetry2, signalled by the nonvanishing quark condensate ⟨ q q ¯ ⟩ , is dynamically generated through topologically nontrivial gauge configurations such as instantons3. The precise mechanism linking the chiral symmetry breaking to the mass generation associated with quark confinement4 remains a profound open question in quantum chromodynamics (QCD)-the fundamental theory of strong interaction. High-energy proton-proton collisions could liberate virtual quark-antiquark pairs from the vacuum that subsequently undergo confinement to form hadrons, whose properties could serve as probes into QCD confinement and the quark condensate. Here we report evidence of spin correlations in Λ Λ ¯ hyperon pairs inherited from spin-correlated strange quark-antiquark virtual pairs. Measurements by the STAR experiment at the Relativistic Heavy Ion Collider (RHIC) at Brookhaven National Laboratory reveal a relative polarization signal of (18 ± 4)% that links the virtual spin-correlated quark pairs from the QCD vacuum to their final-state hadron counterparts. Crucially, this correlation vanishes when the hyperon pairs are widely separated in angle, consistent with the decoherence of the quantum system. Our findings provide a new experimental model for exploring the dynamics and interplay of quark confinement and entanglement.
Keywords: Chiral symmetry breaking; Color confinement; Hadron; Hyperon; QCD vacuum; Quantum chromodynamics; Quark; Spontaneous symmetry breaking; Symmetry breaking; Top quark; dept.phy

Energy independence of the Collins asymmetry in p ↑ p collisions - STAR Collaboration (Physical Review Letters, 2025)
The STAR experiment reports new, high-precision measurements of the transverse single-spin asymmetries for π^{±} within jets, namely the Collins asymmetries, from transversely polarized p^{↑}p collisions at sqrt[s]=510 GeV. The energy-scaled distribution of jet transverse momentum, x_{T}=2p_{T,jet}/sqrt[s], shows a remarkable consistency for Collins asymmetries of π^{±} in jets between sqrt[s]=200 GeV and 510 GeV. This indicates that the Collins asymmetries are nearly energy independent, with, at most, a very weak scale dependence in p^{↑}p collisions. These results extend to high-momentum scales (Q^{2}≤3400 GeV^{2}) and enable unique tests of evolution and universality in the transverse-momentum-dependent formalism, thus providing important constraints for the Collins fragmentation functions.
Keywords: Asymmetry; Consistency (knowledge bases); Fragmentation (computing); High energy; Independence (probability theory); Polarization (electrochemistry); Transverse plane; Universality (dynamical systems); dept.phy

Probing late-stage hadronic interactions at high baryon density via K⁎0 production in the RHIC beam energy scan program - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2026)
A precision measurement of the K ⁎0 meson yield is reported in Au+Au collisions at sNN=7.7,11.5,14.6,19.6, and 27 GeV using the high-statistics data sample collected by the STAR experiment during the Beam Energy Scan II (BES-II) program at RHIC. The transeverse momentum ( pT )-integrated yield ratios (K*0+K*0‾)/(K++K−) in central collisions show a suppression relative to peripheral collisions at the (1.7–3.6) σ level, while a thermal model without final-stage rescattering overpredicts this ratio with a deviation of (6.9–8.2) σ . These results indicate a loss of the measured K ⁎0 signal in central collisions due to re-scattering of its hadronic decay products in the hadronic phase. The pT -integrated yield of charged kaons exhibits an approximate scaling with charged-particle multiplicity, independent of collision energy and system size. A similar trend is observed for the short-lived K ⁎0 resonance, although significant deviations emerge at lower energies. At BES energies, the K ⁎0/ K ratio shows stronger suppression than at the highest RHIC and LHC energies within a given multiplicity bin, particularly in central and mid-central collisions. This behavior is consistent with changes in the effective hadronic interaction cross section and is supported by transport model calculations, which indicate dominant meson–baryon interactions at lower energies and meson–meson interactions at higher energies. Copyright © 2026. Published by Elsevier B.V.
Keywords: BES; Hadronic phase; Heavy ion collisions; Re-scattering; Resonance

Measurement of the longitudinal flow-plane decorrelation using multiplane cumulants in (Formula presented.) = 200 GeV Au + Au, Ru + Ru, and Zr + Zr collisions - STAR Collaboration (Physical Review C, 2026)
Measurements of the variation of anisotropic flow-plane angles (Ψn) with rapidity, commonly known as the flow-plane decorrelation, provide important insights into the initial conditions of the matter produced in heavyion collisions. In this paper, using data collected by the STAR experiment, we report the first measurement of the four-plane correlator observable (Formula presented.), where superscripts a, b, c, and d denote sequential pseudorapidity (η) regions with a corresponding to the most backward region, b and c close to midrapidity with nb < 0 and nc > 0, and d being the most forward. The measurement is performed for the elliptic and triangular flow (i.e., n = 2 and 3) in Au + Au and isobar (Ru + Ru, Zr + Zr) collisions at (Formula presented.) = 200 GeV. The goal of calculating the correlation of the flow-plane angle variations from backward to midcentral, and from midcentral to forward regions, is to probe the systematic variation of flow angle over a wide П range. In midcentral collisions (10-30 % centrality), we find T2{ba; dc} = —0.004 ± 0.001 (stat) ± 0.002(syst) independent of the collision system. Such a small value of T2 favors a “random-walk” variation of the flow-plane angles, where the rapidity correlation length is smaller than the entire region under study. These measurements provide new information on the decorrelation patterns in the system and offer a quantitative estimate of possible systematic variations in anisotropic flow angles such as “twist” between forward and backward regions. This opens new opportunities for understanding the three-dimensional structure and the time evolution of the quarkgluon plasma created in heavy-ion collisions. © 2026 American Physical Society
Keywords: Calibration; Cumulant; Decorrelation; Noise (video); Signal processing; dept.phy

Lignin-derived carbon dots from leaf waste as sustainable plant sunscreens and UV-protective foliar coatings - Thangavelu, Raja; Gray, Sarah; Wu, Binlin; Pellegrino, Richard; da Silva, Washington; Zuverza-Mena, Nubia; Dimkpa, Christian; White, Jason (Environmental Science Nano, 2026)
Keywords: Agricultural waste; Agriculture; Carbon fibers; Lignin; Maple; Sustainable agriculture; Sustainable production; dept.phy

Beam-energy dependence of correlations between mean transverse momentum and anisotropic flow of charged particles in Au+Au collisions at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2026)
The correlation between the mean transverse momentum, [p T], and the squared anisotropic flow, vn2, on an event-by-event basis has been suggested to be influenced by the initial conditions in heavy-ion collisions. We present measurements of the variances and covariance of [p T] and vn2, along with their dimensionless ratio, for Au+Au collisions at various beam energies: sNN = 14.6, 19.6, 27, 54.4, and 200 GeV. Our measurements reveal a distinct energy-dependent behavior in the variances and covariances. In addition, the dimensionless ratio displays a similar behavior across different beam energies. We compare our measurements with hydrodynamic models and similar measurements from Pb+Pb collisions at the Large Hadron Collider (LHC). These findings provide valuable insights into the beam energy dependence of the specific shear viscosity (η / s) and initial-state effects, allowing for differentiating between different initial-state models. © 2026 The Authors.
Keywords: Collectivity; Correlation; Shear viscosity; Transverse momentum correlations; dept.phy

Search for the chiral magnetic effect through beam energy dependence of charge separation using event shape selection - STAR Collaboration (Physical Review C, 2026)
High-energy, heavy-ion collisions can create local domains of chirality-imbalanced quarks, reflecting the topological features of quantum chromodynamics. The chiral magnetic effect (CME) predicts an electric charge separation of quarks in such topological domains along the magnetic field (B) generated by the passing of two high-Z nuclei. We use a correlation observable Δγ112 between charged meson pairs to detect the CME-induced charge separation and a novel event shape selection (ESS) method to mitigate the background effects related to elliptic flow (v2). The ESS method classifies events based on the emission pattern of final-state particles and determines Δγ(Formula presented) from the zero-flow limit. We reconstruct the B field direction from the spectator nucleons, which minimizes backgrounds unrelated to the collective motion of the system. In this work, we report the measurements of Δγ112 and a background indicator Δγ132 in Au + Au collisions from the Brookhaven National Laboratory Relativistic Heavy Ion Collider (RHIC) Beam Energy Scan phase II and at the top RHIC energy. After background suppression, Δγ(Formula presented) aligns with zero, and Δγ(Formula presented) is reduced to no more than 20% of Δγ112. We observe a finite residual charge separation with 2.5σ, 3σ, and 3.2σ significance in the 20-50% centrality range of Au + Au collisions at 11.5, 14.6, and 19.6 GeV. The results at 17.3 and 27 GeV also show positive values but with a lower significance of 1.3σ and 1.1σ, respectively. The corresponding ΔγΈ5ΕΕ values at 7.7, 9.2, and 200 GeV are consistent with zero within uncertainties. © (2026), (American Physical Society). All right reserved.
Keywords: Beam (structure); Charge (physics); Energy (signal processing); Event (particle physics); Magnetic field; Selection (genetic algorithm); dept.phy

Measurement of kaon directed flow in Au+Au collisions in the high baryon density region - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2026)
Rapidity-odd directed flow v 1 measurements are presented for K ± and KS0 in Au + Au collisions for sNN from 3.0 to 3.9 GeV with the STAR experiment. For comparison, v 1 of π ± , protons, and Λ from the same collisions are also discussed. The mid-rapidity v 1 slope dv1/dy|y=0 for protons and Λ is positive in these collisions. On the other hand, v 1 slope of kaons exhibits a strong pT dependence: negative at pT< 0.6 GeV/ c and positive at higher pT. A similar pT dependence is also evident for the v 1 slope of charged pions. Compared to the spectator-removed calculations in Au+Au collisions at sNN= 3.0–3.9 GeV, the JAM model demonstrates a pronounced shift of the v 1 slopes of mesons towards the negative direction. It suggests that the shadowing effect of the spectators plays an important role in the observed kaon anti-flow at low pT in the high baryon density region of non-central collisions. © 2026 The Authors.
Keywords: Directed flow; Heavy-ion collisions; High baryon density region; Kaon potential; QCD phase structure; Spectator effect; dept.phy

Interface-Induced Polarization and Inhibition of Ferroelectricity in Epitaxial SrTiO3/Si - Kolpak, A.M.; Walker, F.J.; Reiner, J.W.; Segal, Y.; Su, D.; Sawicki, M.S.; Broadbridge, C.C.; Zhang, Z.; Zhu, Y.; Ahn, C.H.; Ismail-Beigi, S. (Handbook Of Molecular Beam Epitaxy Of Oxide Materials (In 3 Volumes), 2025)
We use SrTiO3/Si as a model system to elucidate the effect of the interface on ferroelectric behavior in epitaxial oxide films on silicon. Using both first-principles computations and synchrotron x-ray diffraction measurements, we show that structurally imposed boundary conditions at the interface stabilize a fixed (pinned) polarization in the film but inhibit ferroelectric switching. We demonstrate that the interface chemistry responsible for these phenomena is general to epitaxial silicon-oxide interfaces, impacting on the design of silicon-based functional oxide devices. © 2026 by World Scientific Publishing Co. Pte. Ltd.
Keywords: Antiferroelectricity; Epitaxy; Ferroelectricity; Induced polarization; Polarization (electrochemistry); dept.phy

Characterizing TESS-identified Quadruple- and Higher-order Eclipsing Binaries. I. Speckle Imaging with DSSI and HRCam - Majewski, Steven; Davidson, James; Wilson, Robert; Horch, Elliott; McKee, P.; Fagan, Evan; Hartwell, Gary; Kostov, Veselin; Adams, C.; Sutherland, Torrie; Tokovinin, Andreï; Wilson, John (The Astrophysical Journal, 2025)
Abstract NASA’s TESS mission has unveiled a plethora of eclipsing binaries (EBs), among them hundreds of triples and higher-order, hierarchical systems. These complex targets require follow-up observations to enable full characterization of system architectures and identify the most compact multiples expected to undergo the most dramatic dynamical evolution. We report first results from a long-term effort to perform such follow-up, focusing here on multiband speckle imaging of a majority (57) of the sample of 97 quadruple- and higher-order eclipsing binaries (Q+EBs) identified via TESS light curves by V. B. Kostov et al. Diffraction-limited imaging with the Differential Speckle Survey Instrument on the Astrophysical Research Consortium 3.5 m telescope and HRCam on the Southern Astrophysical Research 4.1 m telescope reveals nearly 60% of the 57 to resolve into two sources separated by ≥0 . ″ 03. For these partly resolved systems, we report derived characteristics (e.g., relative position angle, angular separation, and magnitude differences in multiple passbands) from the speckle imaging. We find those Q+EBs partly resolved with 4 m class telescopes to have significantly inflated Gaia parallax errors and large Gaia renormalized unit weight errors, particularly for systems with separations comparable to Gaia’s resolution limit (∼0 . ″ 6). For unresolved systems we report upper limits on angular and linear projected separations. We find two partly resolved Q+EBs with wide linear separations having eclipse timing variations that are therefore candidates of higher-than-quadruple multiplicity. Finally, we demonstrate how speckle imaging of resolved Q+EBs during an eclipse can clarify which speckle-resolved Q+EB subsystem is associated with a particular set of TESS eclipses.
Keywords: Angular resolution (graph drawing); Astrometry; Eclipse; Parallax; Speckle imaging; Speckle pattern; Telescope; dept.phy

Observation of Charmonium Sequential Suppression in Heavy-Ion Collisions at the Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review Letters, 2026)
We report measurements of charmonium sequential suppression in Ru+Ru and Zr+Zr collisions at sNN=200 GeV with the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The inclusive yield ratio of ψ(2S) to J/ψ as a function of transverse momentum is reported, along with the centrality dependence of the double ratio, defined as the ψ(2S) to J/ψ ratio in heavy-ion collisions relative to that in p+p collisions. In the 0-80% centrality class, the double ratio is found to be 0.41±0.10 (stat)±0.03 (syst)±0.02 (ref), lower than unity with a significance of 5.6 standard deviations. This provides experimental evidence that ψ(2S) is significantly more suppressed than J/ψ in heavy-ion collisions at RHIC. This sequential suppression pattern seems to increase from peripheral to central collisions, but with no significant dependence on the transverse momentum. © 2026 American Physical Society.
Keywords: dept.phy

Semi-inclusive direct photon + jet and π0+jet correlations measured in p + p and central Au + Au collisions at √sNN = 200 GeV - STAR Collaboration (Physical Review C, 2026)
The Solenoidal Tracker at RHIC (STAR) experiment at the Relativistic Heavy Ion Collider reports new measurements of jet quenching based on the semi-inclusive distribution of charged-particle jets recoiling from direct photon (γdir) and neutral pion (π0) triggers in pp and central Au + Au collisions at √sNN = 200 GeV for triggers in the range 9 < ET trig < 20 GeV. The datasets have integrated luminosities of 3.9 nb−1 for Au + Au and 23 pb−1 for pp collisions. Jets are reconstructed using the anti-kT algorithm with resolution parameters R = 0.2 and 0.5. The large uncorrelated jet background in central Au + Au collisions is corrected using a mixed-event approach, which enables precise charged-particle jet measurements at low transverse momentum pch T,jet and large R. Recoil-jet distributions are reported in the range pch T,jet < 25 GeV/c. Comparison of the distributions measured in pp and Au + Au collisions reveals strong medium-induced jet yield suppression for R = 0.2 with markedly less suppression for R = 0.5. Comparison is also made to theoretical models incorporating jet quenching. These data provide new insight into the mechanisms underlying jet quenching and the angular dependence of medium-induced jet-energy transport and provide new constraints on modeling such effects. © 2025 American Physical Society
Keywords: Jet (fluid); Mathematics; Physics; Thermodynamics; dept.phy

Nanoelectronics, Nanophotonics, And Quantum Technologies: Devices And Applications - Jain, Faquir C.; Broadbridge, C.; Gherasimova, M.; Tang, Hong (World Scientific, 2025)
This timely compendium provides state-of-the-art articles covering research areas in Nanoelectronics, Nanophotonics and Quantum Technologies.Composed of contributions by renowned researchers from both the academia and industry, this useful reference text broadly illustrates relevant aspects of high-performance materials and emerging quantum and nanoscale devices for implementing high-speed electronic systems.
Keywords: Computers / Quantum Computing; Technology & Engineering / Nanotechnology & MEMS; dept.phy

Optical Molecular Signatures of IDH Genotype for Classification of Human Glioma Using Visible Resonance Raman Spectroscopy - Zhang, Liang; Zhou, Yan; Wu, Binlin; Zhang, Shengjia; Zhu, Ke; Liu, C.; Alfano, Robert; Yu, Xinguang (Journal of Biophotonics, 2026)
Keywords: Biomarker; Gene; Genotype; Glioma; IDH mutation; IDH1; Isocitrate dehydrogenase; Mutation; Raman spectroscopy; Resonance Raman spectroscopy; dept.phy; glioma; optical molecular biopsy; visible resonance Raman spectroscopy

Mass-luminosity anomalies: Plausible evidence of recent stellar interaction in the extraordinary blue straggler S1082 - Quitral-Pierart, Amanda; Leigh, Nathan; Mathieu, Robert; Latham, David; Sandquist, Eric; Horch, Elliott (Astronomy and Astrophysics, 2025)
Context. We present an observational and theoretical study of the complex stellar system S1082 in the open cluster M67. This system consists of at least four stars: a blue straggler in a 1.07-day eclipsing binary with a main sequence star (binary A) and another blue straggler in a 1185-day orbit with an unknown companion (binary B). Aims. We analyzed observational data to obtain the orbital and stellar parameters of the components of the eclipsing system. We then explored mass transfer and dynamical encounter scenarios that could explain the derived properties of all of the components of S1082. Methods. We combined high-precision photometry from K2 and TESS with archival light curves, new radial-velocity measurements, and speckle imaging to refine the orbital and physical parameters of the system. To explore the formation pathways, we conducted binary evolution simulations with MESA and dynamical scattering experiments with FEWBODY, followed by a tidal evolution modeling procedure. Results. Our revised radial-velocity solutions yield significantly changed dynamical masses for binary A, reducing the tension with the cluster turnoff mass compared to previous studies. Speckle imaging shows two resolved components separated by 390 AU in projection and, in combination with the two spectroscopic orbits, this is suggestive of a hierarchical quadruple configuration. Our results suggest that the two blue stragglers formed separately, with later dynamical encounters assembling the present configuration. This work underscores the importance of stellar dynamics in shaping the evolution of complex stellar systems within cluster environments such as M67.
Keywords: Binary number; Binary star; Blue straggler; Blue stragglers; Cluster (spacecraft); Open clusters and associations: individual: M67; Photometry (optics); Speckle imaging; Star cluster; Stars: individual: S1082; Stellar evolution; Stellar mass; dept.phy

Measurement of medium-induced acoplanarity in central Au-Au and pp collisions at √sNN = 200 GeV using direct-photon+jet and π+ jet correlations - STAR Collaboration (Physical Review C, 2026)
The STAR Collaboration reports measurements of acoplanarity using semi-inclusive distributions of charged-particle jets recoiling from direct photon and π triggers, in central Au–Au and pp collisions at √sNN = 200 GeV. Significant medium-induced acoplanarity broadening is observed for large but not small recoil jet resolution parameter, corresponding to recoil jet yield enhancement up to a factor of ≈20 for trigger-recoil azimuthal separation far from π. This phenomenology is indicative of the response of the quark-gluon plasma to excitation, but not the scattering of jets off of its quasiparticles. The measurements are not well described by current theoretical models which incorporate jet quenching. © (2026), (American Physical Society). All rights reserved.
Keywords: Component (thermodynamics); Field (mathematics); Measure (data warehouse); Noise (video); Work (physics); dept.phy

Erratum: Disappearance of partonic collectivity in √ sNN = 3 GeV Au+Au collisions at RHIC (Physics Letters B, (2022), 827, 137003) - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
We report on the measurements of directed flow v1 and elliptic flow v2 for hadrons (π±, K±, KS0, p, ϕ, Λ and Ξ−) from Au+Au collisions at sNN = 3 GeV and v2 for (π±, K±, p and p‾) at 27 and 54.4 GeV with the STAR experiment. While at the two higher energy midcentral collisions the number-of-constituent-quark (NCQ) scaling holds, at 3 GeV the v2 at midrapidity is negative for all hadrons and the NCQ scaling is absent. In addition, the v1 slopes at midrapidity for almost all observed hadrons are found to be positive, implying dominant repulsive baryonic interactions. The features of negative v2 and positive v1 slope at 3 GeV can be reproduced with a baryonic mean-field in transport model calculations. These results imply that the medium in such collisions is likely characterized by baryonic interactions. © 2025 The Authors.
Keywords: Baryonic interactions; Collectivity; High baryon density; NCQ scaling; STAR experiment; dept.phy

Temperature measurement of Quark-Gluon plasma at different stages - STAR Collaboration (Nature Communications, 2025)
In a Quark-Gluon Plasma (QGP), the fundamental building blocks of matter, quarks and gluons, are under extreme conditions of temperature and density. A QGP could exist in the early stages of the Universe, and in various objects and events in the cosmos. The thermodynamic and hydrodynamic properties of the QGP are described by Quantum Chromodynamics (QCD) and can be studied in heavy-ion collisions. Despite being a key thermodynamic parameter, the QGP temperature is still poorly known. Thermal lepton pairs (e+e− and μ+μ−) are ideal penetrating probes of the true temperature of the emitting source, since their invariant-mass spectra suffer neither from strong final-state interactions nor from blue-shift effects due to rapid expansion. Here we measure the QGP temperature using thermal e+e− production at the Relativistic Heavy Ion Collider (RHIC). The average temperature from the low-mass region (in-medium ρ0 vector-meson dominant) is (2.01 ± 0.23) × 1012 K, consistent with the chemical freeze-out temperature from statistical models and the phase transition temperature from Lattice QCD. The average temperature from the intermediate mass region (above the ρ0 mass, QGP dominant) is significantly higher at (3.25 ± 0.60) × 1012 K. This work provides essential experimental thermodynamic measurements to map out the QCD phase diagram and understand the properties of matter under extreme conditions. © The Author(s) 2025.
Keywords: Measure (data warehouse); Phase diagram; Plasma; Quantum chromodynamics; Quark–gluon plasma; Temperature measurement; Thermal; Transition temperature; Work (physics); dept.phy

Measurements of ϒ states production in p + p collisions at √s = 500 GeV with STAR: Cross sections, ratios, and multiplicity dependence - STAR Collaboration (Physical Review D, 2025)
We report measurements of ϒ(1S), ϒ(2S) and ϒ(3S) production in p + p collisions at √s = 500 GeV ffiffi by the STAR experiment in year 2011, corresponding to an integrated luminosity Lint = 13 pb−1. The results provide precise cross sections, transverse momentum (pT) and rapidity (y) spectra, as well as cross section ratios for pT < 10 GeV=c and |y| < 1. The dependence of the ϒ yield on charged particle multiplicity has also been measured, offering new insights into the mechanisms of quarkonium production. The data are compared to various theoretical models: the color evaporation model (CEM) accurately describes the ϒ(1S) production, while the color glass condensate + nonrelativistic quantum chromodynamics (CGC + NRQCD) model overestimates the data, particularly at low pT. Conversely, the color singlet model (CSM) underestimates the rapidity dependence. These discrepancies highlight the need for further development in understanding the production dynamics of heavy quarkonia in high-energy hadronic collisions. The trend in the multiplicity dependence is consistent with CGC/saturation and string percolation models or ϒ production happening in multiple parton interactions modeled by PYTHIA8. © 2025 American Physical Society
Keywords: Algorithm; Mathematics; dept.phy

Precision measurement of the longitudinal double-spin asymmetry for dijet production at intermediate pseudorapidity ffiffi in polarized pp collisions at √s = 200 GeV - STAR Collaboration (Physical Review D, 2025)
The STAR Collaboration reports precise measurements of the longitudinal double-spin asymmetry, ALL, for dijet production with at least one jet at intermediate pseudorapidity 0.8 < ηjet < 1.8 in polarized proton-proton collisions at a center-of-mass energy of 200 GeV. This study explores partons scattered with a longitudinal momentum fraction (x) from 0.01 to 0.5, which are predominantly characterized by interactions between high-x valence quarks and low-x gluons. The results are in good agreement with previous measurements at 200 GeV with improved precision and are found to be consistent with the predictions of global analyses that find the gluon polarization to be positive. In contrast, the negative gluon polarization solution from the JAM Collaboration is found to be strongly disfavored. © 2025 American Physical Society
Keywords: Asymmetry; Computer science; Particle physics; Physics; Production (economics); Pseudorapidity; Spin (aerodynamics)

Hyperon global polarization in isobar Ru+Ru and Zr+Zr collisions at sNN=200GeV - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
The polarization of Λ , Λ ¯ , Ξ − , and Ξ ¯ + hyperons along the angular momentum of the system has been measured in isobar collisions of Ru+Ru and Zr+Zr at s N N = 200 GeV with the STAR detector at RHIC. The polarization dependence on collision centrality exhibits an increasing trend in more peripheral collisions. Λ and Λ ¯ polarization dependence on the transverse momentum and pseudorapidity have been investigated, but no significant dependence was observed. The polarizations of Λ and Λ ¯ are found to be consistent with each other, indicating little contribution of the spin-magnetic coupling to the measured polarization. Comparison to previously measured polarization in Au+Au collisions show no obvious system size dependence. The results are qualitatively consistent with hydrodynamic calculations including contributions from shear-induced polarization and thermal vorticity. For the first time in heavy-ion collisions, the dependence of the global polarization on the hyperon’s emission azimuthal angle relative to the second-order event plane has been measured, indicating stronger polarization for the in-plane emitted hyperons at the level of 2.4 σ significance in 20–50 % centrality. The Ξ hyperon polarization measurements via polarization transfer analysis yield finite positive values with 2.9 σ significance in 20–50 % centrality, slightly larger compared to the inclusive Λ polarization. © 2025 The Authors.
Keywords: Global polarization; Hyperon; Vorticity; dept.phy

Precision Measurement of Net-Proton-Number Fluctuations in Au+Au Collisions at RHIC - STAR Collaboration (Physical review letters, 2025)
We report precision measurements on cumulants (C_{n}) and factorial cumulants (κ_{n}) of (net) proton number distributions up to fourth order in Au+Au collisions over center-of-mass energies sqrt[s_{NN}]=7.7-27  GeV from phase II of the Beam Energy Scan program at RHIC. (Anti)protons are selected at midrapidity (|y|<0.5) within a transverse momentum range of 0.4<p_{T}<2.0  GeV/c. Relative to various noncritical-point model calculations and peripheral collision 70%-80% data, the net proton C_{4}/C_{2} measurement in 0%-5% collisions shows a minimum around 19.6 GeV for significance of deviation at ∼2-5σ. A minimum in C_{4}/C_{2} with respect to a noncritical baseline is expected to be a characteristic feature of the signature associated with a critical point in the QCD phase diagram. In addition, deviations from noncritical baselines around the same collision energy region are also seen in proton factorial cumulant ratios, especially in κ_{2}/κ_{1} and κ_{3}/κ_{1}. Dynamical model calculations including a critical point are called for in order to understand these precision measurements.
Keywords: Net (polyhedron); Nuclear physics; Physics; Proton; dept.phy

HST Proper Motions of Andromeda V and Andromeda VI - Casetti-Dinescu, Dana I.; Pawlowski, Marcel S.; Girard, Terrence M.; Kanehisa, Kosuke Jamie; Martone, Max; Petroski, Alexander (Astrophysical Journal, 2025)
We measure the absolute proper motions of Andromeda V (And V) and Andromeda VI/Pegasus (And VI) dwarf galaxies, satellites of M31 located near its galactic plane. And VI is located the farthest from M31 among the six satellites with currently measured proper motions. A combination of Advanced Camera for Surveys/wide filed channel (WFC) and WFPC2 exposures is utilized, spanning a 20 yr time baseline. The WFPC2 exposures are processed using a recently developed deep-learning centering procedure as well as the most up-to-date astrometric calibration of the camera. We use on the order of 100 background galaxies per satellite to determine the correction to absolute proper motion. For And V, we obtain an absolute proper motion of (μα, μδ)And V= (26.1 ± 21.5 , − 74.2 ± 19.1) μ as yr−1. For And VI, we obtain an absolute proper motion of (μα, μδ)And VI= (− 1.6 ± 12.3 , − 52.6 ± 11.2) μ as yr−1. Orbit integrations and analyses are made for these two Andromeda satellites using two estimates of both the mass and proper motion of M31. It is found that And V has an orbit consistent within errors with alignment with M31’s disk and counter orbiting it, although this alignment is not well constrained. And VI’s orbit is better determined and is very much consistent with coorbiting with M31’s disk. While currently at a distance of ∼280 kpc from M31, And VI will remain beyond a distance of ∼90 kpc from M31, thus experiencing low tidal influence compared to the other M31 satellites with known orbits. Both satellites are determined to be well-bound to M31. © 2025. The Author(s). Published by the American Astronomical Society.
Keywords: dept.phy

Measurement of Two-Point Energy Correlators within Jets in p+p Collisions at sqrt[s]=200 GeV - STAR Collaboration (Physical review letters, 2025)
Hard-scattered partons ejected from high-energy proton-proton collisions undergo parton shower and hadronization, resulting in collimated collections of particles that are clustered into jets. A substructure observable that highlights the transition between the perturbative and nonperturbative regimes of jet evolution in terms of the angle between two particles is the two-point energy correlator (EEC). In this Letter, the first measurement of the EEC at RHIC is presented, using data taken from 200 GeV p+p collisions by the STAR experiment. The EEC is measured both for all the pairs of particles in jets and separately for pairs with like and opposite electric charges. These measurements demonstrate that the transition between perturbative and nonperturbative effects occurs within an angular region that is consistent with expectations of a universal hadronization regime that scales with jet momentum for a given initiator flavor. Additionally, a deviation from Monte Carlo predictions at small angles in the charge-selected sample could result from mechanics of hadronization not fully captured by current models.
Keywords: Collimated light; Hadronization; Jet (fluid); Momentum (technical analysis); Monte Carlo method; Observable; Parton; Parton shower; Substructure; dept.phy

Onset of Constituent Quark Number Scaling in Heavy-Ion Collisions at RHIC - STAR Collaboration (Physical review letters, 2025)
Partonic collectivity is one of the necessary signatures for the formation of quark-gluon plasma in high-energy nuclear collisions. Number of constituent quarks (NCQ) scaling has been observed for hadron elliptic flow v_{2} in top energy nuclear collisions at the Relativistic Heavy Ion Collider and the LHC, and this has been theoretically suggested as strong evidence for partonic collectivity. In this Letter, a systematic analysis of v_{2} of π^{±}, K^{±}, K_{S}^{0}, p, and Λ in Au+Au collisions at sqrt[s_{NN}]=3.2, 3.5, 3.9, and 4.5 GeV, with the STAR experiment at the Relativistic Heavy Ion Collider, is presented. NCQ scaling is markedly violated at 3.2 GeV, consistent with a hadronic-interaction dominated equation of state. However, as the collision energy increases, a gradual evolution to NCQ scaling is observed. This beam-energy dependence of v_{2} for all hadrons studied provides evidence for the onset of dominant partonic interactions by sqrt[s_{NN}]=4.5  GeV.
Keywords: Heavy ion; Ion; Nuclear physics; Particle physics; Physics; Quark; Scaling; Scaling law; dept.phy

The fire blight pathogen Erwinia amylovora enters apple leaves through naturally occurring wounds from the abscission of trichomes - Millett, Felicia; Standish, James; Scanley, Jules; Miller, Katelyn; Inguagiato, John; Zuverza‐Mena, Nubia; Abril, Maritza; Robinson, Victoria; Li, Yan; Sundin, George; Zeng, Quan (The Plant Journal, 2025)
The plant epidermis is a single layer of cells covering all plant organs. How pathogens overcome this barrier and enter plants is an important aspect of plant-pathogen interactions. For bacterial plant pathogens, known entry points include natural openings, such as stomata, hydathodes, and mechanical injuries caused by insect feeding, wind damage, or hailstorms. Here, we report that the fire blight pathogen Erwinia amylovora enters apple leaves through naturally occurring wounds caused by the abscission of trichomes during the course of leaf development. Through macroscopic and microscopic observations, we depicted a clear invasion path for E. amylovora cells, from epiphytic growth on glandular trichomes (GT) and non-glandular trichomes (NT) to entry through wounds caused by abscised trichomes, into the epithem, and subsequent spread through xylem. We further observed that GT and NT undergo an abscission process, and that the amount of naturally occurring wounds during abscission is associated with the increase in E. amylovora population. Key genes important for the colonization of GT and NT were identified. The contribution of the type III secretion system and amylovoran biosynthesis during GT colonization was validated. Our findings propose a novel host entry mechanism of plant pathogenic bacteria through naturally occurring wounds during the abscission of plant surface structures.
Keywords: Abscission; Blight; Colonization; Erwinia; Erwinia amylovora; Fire blight; Trichome; abscission; dept.phy; fire blight; host entry points; trichomes; type III secretion system

Effect of binder concentration on ternary MnO2/CuS/reduced graphene oxide material for supercapacitor applications - Chaudhary, Manika; Oyelola, Lekan; Glidden, Thomas; Broadbridge, C.; LeMaire, Peter; Sharma, Rakesh; Singh, Vinamrita; Sahi, Vikhyat; Singhal, Rahúl (Journal of Solid State Electrochemistry, 2025)
Keywords: Capacitance; Chemical engineering; Chemistry; Electrochemistry; Electrode; Energy storage; Graphene; Inorganic chemistry; Materials science; Metallurgy; Nanotechnology; Oxide; Physical chemistry; Supercapacitor; Synthesis; Ternary operation; Thermodynamics; X-ray diffraction; dept.phy

Photon counting in stellar intensity interferometry: current status and future prospects - Horch, Elliott P. (Advanced Photon Counting Techniques XIX, 2025)
Intensity interferometry, also known as the Hanbury Brown and Twiss effect, has seen significant interest in astronomy in recent years. The method involves recording timing correlations between photons received at two or more telescopes in order to derive extremely high spatial resolution information about an astronomical object, potentially including imaging stellar surfaces and other objects at unprecedented scales. This paper will briefly review the technique, discuss the performance characteristics of the of photon counters used in modern intensity interferometers, and describe opportunities for the future. As an example of photon counting with a working instrument, observing experiences with the Southern Connecticut Stellar Interferometer (SCSI), a three-station instrument using single-photon avalanche diode (SPAD) detectors, will be described. The recent lessons learned with this and other instruments in use today give a clear picture of the next steps needed to upgrade efficiency and successfully observe fainter objects. If successful, these improvements would provide a strong argument for creating situations where intensity interferometers can have baselines of one to several kilometers, which would unlock the spatial detail needed to address several exciting astrophysical questions.
Keywords: Astronomy; Current (fluid); Intensity (physics); Interferometry; Optics; Photon; Photon counting; Physics; dept.phy

The Qz5 Survey. I. How the H i Mass Density of the Universe Evolves with Cosmic Time - Oyarzún, Grecco A.; Rafelski, Marc; Christensen, Lise; Ozyurt, Fiona; Jorgenson, Regina A.; Neeleman, M.; Fumagalli, Michele; Prochaska, J. Xavier; Worseck, G.; Wisz, M. E.; Becker, George D.; López, Sebastián (The Astrophysical Journal, 2025)
We report that the neutral hydrogen (H i) mass density of the Universe (ρH i) increases with cosmic time since z ∼ 5, peaks at z ∼ 3, and then decreases toward z ∼ 0. This is the first result of Qz5, our spectroscopic survey of 63 quasars at z ≳ 5 with VLT/X-SHOOTER and Keck/ESI aimed at characterizing intervening H i gas absorbers at z ∼ 5. The main feature of Qz5 is the high resolution (R ∼ 7000–9000) of the spectra, which allows us to (1) accurately detect high column density H i gas absorbers in an increasingly neutral intergalactic medium at z ∼ 5 and (2) determine the reliability of previous ρH i measurements derived with lower resolution spectroscopy. We find five intervening damped Lyα absorbers (DLAs) at z > 4.5, which corresponds to the lowest DLA incidence rate () at z ≳ 2. We also measure the lowest ρH i at z ≳ 2 from our sample of DLAs and subDLAs, corresponding to ρH i Mpc−3 at z ∼ 5. Taking into account our measurements at z ∼ 5 and systematic biases in the DLA detection rate at lower spectral resolutions, we conclude that ρH i doubles from z ∼ 5 to z ∼ 3. From these results emerges a qualitative agreement between how the cosmic densities of H i gas mass, molecular gas mass, and star formation rate build up with cosmic time.
Keywords: dept.phy; peer-reviewed

The Solar Neighborhood. LII. M Dwarf Twin Binaries—Presumed Identical Twins Appear Fraternal in Variability, Rotation, Hα, and X-Rays - Couperus, Andrew A.; Henry, Todd J.; Osten, Rachel A.; Jao, Wei-Chun; Vrijmoet, Eliot Halley; Kar, Aman; Horch, Elliott (The Astronomical Journal, 2024)
We present an investigation into the rotation and stellar activity of four fully convective M dwarf “twin” wide binaries. Components in each pair have (1) astrometry confirming they are common-proper-motion binaries, (2) Gaia BP, RP, and 2MASS J, H, and K s magnitudes matching within 0.10 mag, and (3) presumably the same age and composition. We report long-term photometry, rotation periods, multiepoch Hα equivalent widths, X-ray luminosities, time series radial velocities, and speckle observations for all components. Although it might be expected for the twin components to have matching magnetic attributes, this is not the case. Decade-long photometry of GJ 1183 AB indicates consistently higher spot activity on A than B, a trend matched by A appearing 58% ± 9% stronger in L X and 26% ± 9% stronger in Hα on average—this is despite similar rotation periods of A = 0.86 day and B = 0.68 day, thereby informing the range in activity for otherwise identical and similarly rotating M dwarfs. The young β Pic Moving Group member 2MA 0201+0117 AB displays a consistently more active B component that is 3.6 ± 0.5 times stronger in L X and 52% ± 19% stronger in Hα on average, with distinct rotation at A = 6.01 days and B = 3.30 days. Finally, NLTT 44989 AB displays remarkable differences with implications for spindown evolution—B has sustained Hα emission while A shows absorption, and B is ≥39 ± 4 times stronger in L X, presumably stemming from the surprisingly different rotation periods of A = 38 days and B = 6.55 days. The last system, KX Com, has an unresolved radial velocity companion, and is therefore not a twin system.
Keywords: dept.phy; peer-reviewed

Plant-engineered ZnO and CuO nanoparticles exhibit pesticidal activity and mitigate Fusarium infestation in soybean: A mechanistic understanding - Karmous, Inès; Elmer, Wade; Zuverza‐Mena, Nubia; Vaidya, Shital; Tlahig, Samir; Scanley, Jules; Bharadwaj, Anuja; White, Jason; Dimkpa, Christian (Plant Physiology and Biochemistry, 2025)
Keywords: Antifungal activity; Artemisia vulgaris; Biogenic copper and Zn oxide nanoparticles; Biology; Botany; Chemistry; Fusarium; Infestation; Materials science; Nanoparticle; Nanotechnology; Soybean; dept.phy; peer-reviewed

HST Proper Motion of Andromeda III. Another Satellite Coorbiting the M31 Satellite Plane - Casetti-Dinescu, Dana I.; Pawlowski, Marcel S.; Girard, Terrence M.; Kanehisa, Kosuke Jamie; Petroski, Alexander; Martone, Max; Kozhurina-Platais, Vera; Platais, Imants (The Astrophysical Journal, 2024)
We measure the absolute proper motion of Andromeda III (And III) using Advanced Camera for Surveys/Wide Field Channel and WFPC2 exposures spanning an unprecedented 22 yr time baseline. The WFPC2 exposures have been processed using a deep-learning centering procedure recently developed as well as an improved astrometric calibration of the camera. The absolute proper motion zero point is given by 98 galaxies and 16 Gaia EDR3 stars. The resulting proper motion is (μ α , μ δ ) = (−10.5 ± 12.5, 47.5 ± 12.5) μas yr−1. We perform an orbit analysis of And III using two estimates of M31's mass and proper motion. We find that And III’s orbit is consistent with dynamical membership to the Great Plane of Andromeda system of satellites although with some looser alignment compared to the previous two satellites NGC 147 and NGC 185. And III is bound to M31 if M31's mass is M vir ≥ 1.5 × 1012 M ⊙.
Keywords: dept.phy; peer-reviewed

JWST/NIRCam 4–5 μm Imaging of the Giant Planet AF Lep b - Franson, Kyle; Balmer, William O.; Bowler, Brendan P.; Pueyo, Laurent; Zhou, Yifan; Rickman, Emily; Zhang, Zhoujian; Mukherjee, Sagnick; Pearce, Tim D.; Gagliuffi, Daniella C. Bardalez; Biddle, Lauren I.; Brandt, Timothy D.; et al. (The Astrophysical Journal Letters, 2024)
With a dynamical mass of 3 M Jup, the recently discovered giant planet AF Lep b is the lowest-mass imaged planet with a direct mass measurement. Its youth and spectral type near the L/T transition make it a promising target to study the impact of clouds and atmospheric chemistry at low surface gravities. In this work, we present JWST/NIRCam imaging of AF Lep b. Across two epochs, we detect AF Lep b in F444W (4.4 μm) with signal-to-noise ratios of 9.6 and 8.7, respectively. At the planet’s separation of 320 mas during the observations, the coronagraphic throughput is ≈7%, demonstrating that NIRCam’s excellent sensitivity persists down to small separations. The F444W photometry of AF Lep b affirms the presence of disequilibrium carbon chemistry and enhanced atmospheric metallicity. These observations also place deep limits on wider-separation planets in the system, ruling out 1.1 M Jup planets beyond 15.6 au (0.″58), 1.1 M Sat planets beyond 27 au (1″), and 2.8 M Nep planets beyond 67 au (2.″5). We also present new Keck/NIRC2 imaging of AF Lep b; combining this with the two epochs of F444W photometry and previous Keck photometry provides limits on the long-term 3–5 μm variability of AF Lep b on timescales of months to years. AF Lep b is the closest-separation planet imaged with JWST to date, demonstrating that planets can be recovered well inside the nominal (50% throughput) NIRCam coronagraph inner working angle.
Keywords: dept.phy

Observation of the antimatter hypernucleus H¯Λ¯4 - STAR Collaboration (Nature, 2024)
At the origin of the Universe, an asymmetry between the amount of created matter and antimatter led to the matter-dominated Universe as we know it today. The origins of this asymmetry remain unknown so far. High-energy nuclear collisions create conditions similar to the Universe microseconds after the Big Bang, with comparable amounts of matter and antimatter1–6. Much of the created antimatter escapes the rapidly expanding fireball without annihilating, making such collisions an effective experimental tool to create heavy antimatter nuclear objects and to study their properties7–14, hoping to shed some light on the existing questions on the asymmetry between matter and antimatter. Here we report the observation of the antimatter hypernucleus $${}_{\bar{Λ }}{}^{4}\bar{{\rm{H}}}$$, composed of a $$\bar{Λ }$$, an antiproton and two antineutrons. The discovery was made through its two-body decay after production in ultrarelativistic heavy-ion collisions by the STAR experiment at the Relativistic Heavy Ion Collider15,16. In total, 15.6 candidate $${}_{\bar{Λ }}{}^{4}\bar{{\rm{H}}}$$antimatter hypernuclei are obtained with an estimated background count of 6.4. The lifetimes of the antihypernuclei $${}_{\bar{Λ }}{}^{3}\bar{{\rm{H}}}$$and $${}_{\bar{Λ }}{}^{4}\bar{{\rm{H}}}$$are measured and compared with the lifetimes of their corresponding hypernuclei, testing the symmetry between matter and antimatter. Various production yield ratios among (anti)hypernuclei (hypernuclei and/or antihypernuclei) and (anti)nuclei (nuclei and/or antinuclei) are also measured and compared with theoretical model predictions, shedding light on their production mechanisms.
Keywords: Experimental nuclear physics; Experimental particle physics; dept.phy; peer-reviewed

The orbit and dynamical mass of polaris: Observations with the CHARA array - Evans, Nancy Remage; Schaefer, Gail H.; Gallenne, Alexandre; Torres, Guillermo; Horch, Elliott P.; Anderson, Richard I.; Monnier, John D.; Roettenbacher, Rachael M.; Baron, Fabien; Anugu, Narsireddy; Davidson, James W.; Kervella, Pierre; et al. (The Astrophysical Journal, 2024)
The 30 yr orbit of the Cepheid Polaris has been followed with observations by the Center for High Angular Resolution Astronomy (CHARA) Array from 2016 through 2021. An additional measurement has been made with speckle interferometry at the Apache Point Observatory. Detection of the companion is complicated by its comparative faintness—an extreme flux ratio. Angular diameter measurements appear to show some variation with pulsation phase. Astrometric positions of the companion were measured with a custom grid-based model-fitting procedure and confirmed with the CANDID software. These positions were combined with the extensive radial velocities (RVs) discussed by Torres to fit an orbit. Because of the imbalance of the sizes of the astrometry and RV data sets, several methods of weighting are discussed. The resulting mass of the Cepheid is 5.13 ± 0.28 M ⊙. Because of the comparatively large eccentricity of the orbit (0.63), the mass derived is sensitive to the value found for the eccentricity. The mass combined with the distance shows that the Cepheid is more luminous than predicted for this mass from evolutionary tracks. The identification of surface spots is discussed. This would give credence to the identification of a radial velocity variation with a period of approximately 120 days as a rotation period. Polaris has some unusual properties (rapid period change, a phase jump, variable amplitude, and unusual polarization). However, a pulsation scenario involving pulsation mode, orbital periastron passage, and low pulsation amplitude can explain these characteristics within the framework of pulsation seen in Cepheids.
Keywords: dept.phy; peer-reviewed

Optical spectroscopic analysis of cerebrospinal fluid of human brain tumor using visible resonance Raman spectroscopy - Zhou, Y.; Wu, B.; Zhang, L.; Zhu, K.; Zhang, S.; Wang, X.; Zhang, C.; Liu, C.-H.; Yu, X.; Alfano, R.R. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2024)
Currently, liquid biopsy method is mainly used for tumor detection based on genomic molecular alterations in vitro. Liquid biopsy is superior to traditional tissue biopsy techniques and its diagnosis time of disease and repeated diagnosis of liquid biopsy are new breakthroughs in clinical application. Liquid biopsy method can be used to detect most human disease based on genetic biomarkers from body fluids, among which, special biomarkers in blood and cerebrospinal fluid (CSF) samples are the main research objects, and have made good achievements in preliminary clinical applications. The application of optical spectroscopy in the field of liquid biopsy has aroused great interest among researchers and demonstrated the potential of its clinical application for oncology. The aim of this study is to reveal the optical spectroscopic characteristics of the main biochemical components of CSF of brain tumor using visible resonance Raman (VRR) spectroscopy ex vivo. Tumor-associated proteins, glucose, lactate and other metabolites released to CSF can be used as markers for liquid biopsy. We studied the VRR spectra of CSF samples from 7 types of brain tumor patients. The characteristic VRR modes that were found and may be used as a combination of multiple analyte biomarkers include amyloid-β and tau protein, excess neurotransmitters such as glutamic acid derived from the exchange with interstitial fluid (ISF), DNA, glucose, lactate, etc. for optical liquid biopsy analyses. Another interesting finding was that CSF of different types of tumors showed different images similar to the crystallization of water under the optical microscope. Considering our previous study, the current study on CSF provides another proof that the VRR system can provide a complete scan region of 200 - 4000cm-1 as a clinical tool for non-invasive diagnosis of brain disease. © 2024 SPIE.
Keywords: Optical liquid biopsy; amyloid-β (Aβ); cerebrospinal fluid (CSF) ex vivo; dept.phy; glioblastoma (GBM); human brain tumor; tau proteins; visible resonance Raman (VRR) spectroscopy

Star image centering with deep learning. II. HST/WFPC2 full field of view - Casetti-Dinescu, D.I.; Baena-Gallé, R.; Girard, T.M.; Cervantes-Rovira, A.; Todeasa, S. (Publications of the Astronomical Society of the Pacific, 2024)
We present an expanded and improved deep-learning (DL) methodology for determining centers of star images on Hubble Space Telescope/Wide-Field Planetary Camera 2 (WFPC2) exposures. Previously, we demonstrated that our DL model can eliminate the pixel-phase bias otherwise present in these undersampled images; however that analysis was limited to the central portion of each detector. In the current work we introduce the inclusion of global positions to account for the point-spread function (PSF) variation across the entire chip and instrumental magnitudes to account for nonlinear effects such as charge transfer efficiency. The DL model is trained using a unique series of WFPC2 observations of globular cluster 47 Tuc, data sets comprising over 600 dithered exposures taken in each of two filters—F555W and F814W. It is found that the PSF variations across each chip correspond to corrections of the order of ∼100 mpix, while magnitude effects are at a level of ∼10 mpix. Importantly, pixel-phase bias is eliminated with the DL model; whereas, with a classic centering algorithm, the amplitude of this bias can be up to ∼40 mpix. Our improved DL model yields star-image centers with uncertainties of 8-10 mpix across the full field of view of WFPC2. © 2024. The Astronomical Society of the Pacific. All rights reserved.
Keywords: dept.phy; peer-reviewed

Measurements of the Z0/γ⁎ cross section and transverse single spin asymmetry in 510 GeV p + p collisions - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2024)
The differential cross section for Z0 production, measured as a function of the boson's transverse momentum (pT), provides important constraints on the evolution of the transverse momentum dependent parton distribution functions (TMDs). The transverse single spin asymmetry (TSSA) of the Z0 is sensitive to one of the polarized TMDs, the Sivers function, which is predicted to have the opposite sign in p+p →W/Z+X from that which enters in semi-inclusive deep inelastic scattering. In this Letter, the STAR Collaboration reports the first measurement of the Z0/γ⁎ differential cross section as a function of its pT in p+p collisions at a center-of-mass energy of 510 GeV, together with the Z0/γ⁎ total cross section. We also report the measurement of Z0/γ⁎ TSSA in transversely polarized p+p collisions at 510 GeV. © 2024
Keywords: Cross section; Sivers function; Transverse momentum dependent parton distribution functions (TMDs); Transverse single spin asymmetry (TSSA, AN); Z0; dept.phy; peer-reviewed

Human glioma tumor diagnosis using visible resonance Raman spectroscopy and deep learning - Llanos, N.E.; Zhou, Y.; Yu, X.; Zhang, S.; Zhu, K.; Liu, C.-H.; Wu, B.; Alfano, R.R. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2024)
Convolutional neural network (CNN) based deep learning is used to analyze spectral data collected by visible resonance Raman (VRR) spectroscopy to distinguish human glioma tumors from healthy brain tissues using binary classification and identify the cancer grades of the glioma tumors using multi-class classification. Classification was performed using both raw spectral data and baseline-subtracted data for comparison. The classification using both datasets yielded high accuracy, with the results obtained from baseline subtracted spectra slightly better than that obtained from raw spectra. The study showed VRR combined with deep learning provides a robust molecular diagnostic tool for accurately distinguishing glioma tumors from normal tissues and glioma tumor tissues at different cancer grades. Deep learning aided VRR technique may be used for in-situ intraoperative diagnosis of brain cancer. It may help a surgeon to identify cancer margins and even cancer grades during surgery. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.
Keywords: cancer grading; convolutional neural network; deep learning; dept.phy; glioma tumor; human brain tissues; machine learning; optical molecular pathology; peer-reviewed; visible resonance Raman (VRR)

Results on elastic cross sections in proton–proton collisions at s=510 GeV with the STAR detector at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2024)
We report results on an elastic cross section measurement in proton–proton collisions at a center-of-mass energy s=510 GeV, obtained with the Roman Pot setup of the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The elastic differential cross section is measured in the four-momentum transfer squared range 0.23≤−t≤0.67 GeV2. This is the only measurement of the proton-proton elastic cross section in this t range for collision energies above the Intersecting Storage Rings (ISR) and below the Large Hadron Collider (LHC) colliders. We find that a constant slope B does not fit the data in the aforementioned t range, and we obtain a much better fit using a second-order polynomial for B(t). This is the first measurement below the LHC energies for which the non-constant behavior B(t) is observed. The t dependence of B is also determined using six subintervals of t in the STAR measured t range, and is in good agreement with the phenomenological models. The measured elastic differential cross section dσ/dt agrees well with the results obtained at s=540 GeV for proton–antiproton collisions by the UA4 experiment. We also determine that the integrated elastic cross section within the STAR t-range is σelfid=462.1±0.9(stat.)±1.1(syst.)±11.6(scale) μb. © 2024
Keywords: B-slope; Diffraction; Elastic scattering; Proton–proton collisions; dept.phy; peer-reviewed

Jet-hadron correlations with respect to the event plane in sNN =200 GeV Au+Au collisions in STAR - STAR Collaboration (Physical Review C, 2024)
Angular distributions of charged particles relative to jet axes are studied in sNN=200 GeV Au+Au collisions as a function of the jet orientation with respect to the event plane. This differential study tests the expected path-length dependence of energy loss experienced by a hard-scattered parton as it traverses the hot and dense medium formed in heavy-ion collisions. A second-order event plane is used in the analysis as an experimental estimate of the reaction plane formed by the collision impact parameter and the beam direction. Charged-particle jets with 15<pT,jet<20 and 20<pT,jet<40GeV/c were reconstructed with the anti-kT algorithm with radius parameter setting of R=0.4 in the 20-50% centrality bin to maximize the initial-state eccentricity of the interaction region. The reaction plane fit method is implemented to remove the flow-modulated background with better precision than prior methods. Yields and widths of jet-associated charged-hadron distributions are extracted in three angular bins between the jet axis and the event plane. The event-plane (EP) dependence is further quantified by ratios of the associated yields in different EP bins. No dependence on orientation of the jet axis with respect to the event plane is seen within the uncertainties in the kinematic regime studied. This finding is consistent with a similar experimental observation by ALICE in sNN = 2.76 TeV Pb-Pb collision data. © 2024 American Physical Society.
Keywords: dept.phy; peer-reviewed

Observations with the Differential Speckle Survey Instrument. XI. First uear of observations from Apache Point Observatory - Davidson, James W.; Horch, Elliott P.; Majewski, Steven R.; Fagan, Evan; Shea, Melissa A.; Sutherland, Torrie; Wilson, Robert F.; Lesley, D. Xavier; Pellegrino, Richard A.; Leonard, Jonathan P.; Wilson, John C.; Chanover, Nancy J.; et al. (The Astronomical Journal, 2024)
The Differential Speckle Survey Instrument (DSSI) was relocated to the Astrophysical Research Consortium 3.5 m telescope at Apache Point Observatory (APO) in early 2022. Here we present results from the first year of observations along with an updated instrument description for DSSI at APO, including a detailed description of a new internal slit mask assembly used to measure the instrument plate scale from first principles. Astrometric precision for DSSI at APO during this time was measured to be 2.06 ± 0.11 mas, with a photometric precision of 0.14 ± 0.04 mag. Results of 40 resolved binary systems are reported, including two that were previously unknown to be binaries: HIP 7535 and HIP 9603. We also present updated orbital fits for two systems: HIP 93903 and HIP 100714. Finally, we report updated or confirmed dispositions for five Kepler Objects of Interest (KOIs) that were previously explored in Colton et al., using speckle imaging to discern common proper motions pairs from line of sight companions: KOI-270, KOI-959, KOI-1613, KOI-1962, and KOI-3214AB.
Keywords: dept.phy

The POKEMON Speckle Survey of nearby M Dwarfs. II. Observations of 1125 targets - Clark, Catherine A.; Belle, Gerard T. van; Horch, Elliott P.; Lund, Michael B.; Ciardi, David R.; Braun, Kaspar von; Winters, Jennifer G.; Everett, Mark E.; Hartman, Zachary D.; Llama, Joe (The Astronomical Journal, 2024)
Stellar multiplicity is correlated with many stellar properties, yet multiplicity measurements have proven difficult for the M dwarfs—the most common type of star in our galaxy—due to their faintness and the fact that a reasonably complete inventory of later M dwarfs did not exist until recently. We have therefore carried out the Pervasive Overview of “Kompanions” of Every M dwarf in Our Neighborhood (POKEMON) survey, which made use of the Differential Speckle Survey Instrument on the 4.3 m Lowell Discovery Telescope, along with the NN-EXPLORE Exoplanet Stellar Speckle Imager on the 3.5 m WIYN telescope. The POKEMON sample is volume limited from M0V through M9V out to 15 pc, with additional brighter targets at larger distances. In total, 1125 targets were observed. New discoveries were presented in the first paper in the series. In this second paper in the series, we present all detected companions, gauge our astrometric and photometric precision, and compare our filtered and filterless speckle observations. We find that the majority (58.9%) of the companions we detect in our speckle images are not resolved in Gaia, demonstrating the need for high-resolution imaging in addition to long-term astrometric monitoring. Additionally, we find that the majority (73.2%) of simulated stellar companions would be detectable by our speckle observations. Specifically within 100 au, we find that 70.3% of simulated companions are recovered. Finally, we discuss future directions of the POKEMON survey.
Keywords: dept.phy; peer-reviewed

Longitudinal and transverse spin transfer to Λ and ¯Λ hyperons in polarized p+p collisions at √s=200 GeV - STAR Collaboration (Physical Review D, 2024)
The longitudinal and transverse spin transfers to Λ (¯Λ) hyperons in polarized proton-proton collisions are expected to be sensitive to the helicity and transversity distributions, respectively, of (anti)strange quarks in the proton, and to the corresponding polarized fragmentation functions. We report improved measurements of the longitudinal spin transfer coefficient, DLL, and the transverse spin transfer coefficient, DTT, to Λ and ¯Λ in polarized proton-proton collisions at √s=200 GeV by the STAR experiment at RHIC. The dataset includes longitudinally polarized proton-proton collisions with an integrated luminosity of 52pb−1, and transversely polarized proton-proton collisions with a similar integrated luminosity. Both datasets have about twice the statistics of previous results and cover a kinematic range of |η Λ(¯Λ)|<1.2 and transverse momentum pT,Λ(¯Λ) up to 8 GeV/c. We also report the first measurements of the hyperon spin transfer coefficients DLL and DTT as a function of the fractional jet momentum z carried by the hyperon, which can provide more direct constraints on the polarized fragmentation functions.
Keywords: dept.phy; peer-reviewed

Studies of reduced graphene oxide (rGO)/CuS nanocomposite for supercapacitor applications - Singhal, R.; Thorne, D.; Chaudhary, M.; Kumar, A.; Bhardwaj, S.; Abazi, R.; Colon, A.; Gupta, R.K.; Scanley, J.; Broadbridge, C.C.; Singh, B.P.; LeMaire, P.K.; et al. (AIP Advances, 2023)
We have prepared CuS and CuS-rGO nanocomposites via the hydrothermal method. The physical properties of the synthesized materials were studied through x-ray diffraction and scanning electron microscopy. The supercapacitor characteristics were evaluated by cyclic voltammetric and galvanostatic charge–discharge studies. The cyclic voltammetric studies conform the pseudocapacitive nature of CuS and CuS-rGO electrodes. The specific capacitance of CuS was obtained as 207, 150, and 97 F/g at a current density of 0.5, 5, and 20 A/g, respectively. The rGO-CuS nanocomposite showed improved specific capacitance of 350, 251, and 149 F/g at current densities of 0.5, 5, and 20 A/g, respectively. © 2023 Author(s).
Keywords: dept.phy; peer-reviewed

Optimization of manganese dioxide-multiwall carbon nanotube composite electrodes for supercapacitor applications - Singhal, R.; Sadowski, T.; Chaudhary, M.; Tucci, R.V.; Scanley, J.; Patel, R.; Kumar Patel, P.; Gagnon, S.; Koni, A.; Singhal, K.; LeMaire, P.K.; Kumar Sharma, R.; et al. (Materials Science for Energy Technologies, 2024)
Manganese dioxide-multiwall carbon nanotube (MnO2-MWCNT) nanocomposites were synthesized via one-pot synthesis method with varying concentrations of 1 mg/ml, 4 mg/ml, and 10 mg/ml MWCNT. The synthesized nanocomposites were characterized using x-ray diffraction (XRD), transmission electron microscopy (TEM), and electrochemical measurements. The intent of studying different concentrations is, ultimately, to correlate the effect of the concentration of multiwall carbon nanotube on the electrochemical performance of the MnO2-MWCNT nanocomposites. Two primary phenomena were observed as CNT concentration increased. First, less crystalline MnO2 adsorption onto individual CNTs occurred. Subsequently, CNT agglomeration became the primary feature of the nanostructures of high CNT concentration. The electrochemical studies reveal that the specific capacitance of MnO2 increases from 124 F/g to 145 F/g by the addition of 1 mg/ml MWCNTs and decreases to 102 F/g for MnO2-10 mg/ml MWCNT nanocomposite. © 2023
Keywords: Carbon nanotube; MnO2; Specific capacitance; Supercapacitor; TEM; dept.phy; peer-reviewed

Effect of reduce graphene oxide (Rgo) on electrochemical performance of Cus for supercapacitor applications - Singhal, Rahul; Thorne, David; Chaudhary, Manika; Bhardwaj, Shiva; Abazi, Rilind; Gupta, Ram K.; Scanley, Jules; Broadbridge, Christine C.; Singh, B. P.; LeMaire, Peter K.; Sharma, Rakesh K. (2023)
CuS and CuS-rGO nanocomposites were synthesized by the hydrothermal method. The synthesized CuS and rGO-CuS nanocomposite materials were physically characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) and were evaluated electrochemically for supercapacitor applications. The specific capacitance of CuS was determined to be 207 F/g, 150 F/g, and 97 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively. The rGO-CuS nanocomposite showed improved specific capacitance of 350 F/g, 251 F/g, and 149 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively.
Keywords: CuS; SEM; Supercapacitors; dept.phy; rGO; specific capacitance

A New Stellar Companion to GJ 835 - Clark, Catherine A.; Horch, Elliott; Davidson, James W. (Research notes of the AAS, 2023)
Keywords: dept.phy

Nanotechnology in Electronics, Photonics, Biosensors and Energy Systems - Jain, F.; Braodbridge, C.; Gherasimova, M.; Hong, X. Tang (2023)
Keywords: dept.phy

Experimental Status of the Chiral Magnetic Effect - Finch, Evan (EDP Sciences, 2023)
Keywords: dept.phy

Orbits of M Dwarf Binaries Big and Small: Revealing Their Sizes and Shapes Via a Multi-Pronged Observing Campaign - Vrijmoet, Eliot; Henry, Todd; Tokovinin, Andrei; Dieterich, Serge; Horch, Elliott; Jao, Wei-Chun; Winters, Jennifer; Team, Recons (Bulletin of the American Astronomical Society, 2022)
Presentation #205.10 in the session Binary Stellar System - iPoster Session.
Keywords: dept.phy; ⛔ No DOI found

The RKSTAR Concert — A RECONS Survey of the 5000 Nearest K Dwarfs - Henry, Todd; Casetti-Dinescu, Dana; Horch, Elliott; Hubbard-James, Hodari-Sadiki; Jao, Wei-Chun; Lesley, D. Xavier; Paredes, Leonardo; Shea, Melissa; Sutherland, Torrie; Team, Recons (Bulletin of the American Astronomical Society, 2022)
Presentation #305.15 in the session Stars, Cool Dwarfs, Brown Dwarfs — iPoster Session.
Keywords: dept.phy; ⛔ No DOI found

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (Nanostructures For Electronics, Photonics, Biosensors, And Emerging Systems Applications, 2022)
Keywords: dept.phy

Erratum to: Evidence of mass ordering of charm and bottom quark energy loss in Au+Au collisions at RHIC - STAR Collaboration (The European Physical Journal C, 2023)
Keywords: dept.phy; peer-reviewed

Interactions between two adjacent convection rolls in turbulent Rayleigh-Bénard convection - Brown, Eric; Ji, Dandan (Physical Review Fluids, 2023)
We seek to develop a low-dimensional model for the interactions between horizontally adjacent turbulent convection rolls. This was tested in Rayleigh-Bénard convection experiments with two adjacent cubic cells with a partial wall in between. Observed stable states include both counterrotating and corotating states for Rayleigh number 7.6×107< Ra <3.5×109 and Prandtl number 6.41. The stability of each of these states and their dynamics can be modeled low-dimensionally by stochastic ordinary differential equations of motion in terms of the orientation, amplitude, and mean temperature of each convection roll. The form of the interaction terms is predicted based on an effective turbulent diffusion of temperature between the adjacent rolls, which is projected onto the neighboring rolls with sinusoidal temperature profiles. With measurements of a constant coefficient for effective thermal turbulent diffusion, quantitative predictions are made for the nine forcing terms which affect stable fixed points of the corotating and counterrotating states for 5.5×108< Ra <3.5×109. Predictions are found to be accurate within a factor of 3 of experiments. This suggests that the same turbulent thermal diffusivity that describes macroscopically averaged heat transport also controls the interactions between neighboring convection rolls. The surprising stability of corotating states is due to the temperature difference between the neighboring rolls becoming large enough that the heat flux between the rolls stabilizes the temperature profile of aligned corotating states. This temperature difference can be driven with an asymmetry, for example, by heating the plates of the two cells to different mean temperatures. When such an asymmetry is introduced, it also shifts the orientations of the rolls of counterrotating states in opposite directions away from their preferred orientation, which is otherwise due to the geometry of the cell. As the temperature difference between the plates of the different cells is increased, the shift in orientation increases until the counterrotating states become unstable and only corotating states are stable. At very large temperature differences between cells, both the counterrotating and predicted corotating states become unstable; instead we observe a corotating state with much larger temperature difference between the rolls that cannot be explained by turbulent thermal diffusion. Spontaneous switching between corotating and counterrotating states is also observed, including in nominally symmetric systems. Switching to counterrotating states occurs mainly due to cessation (a significant weakening of a convection roll), which reduces damping on changes in orientation, allowing the orientation to change rapidly due to diffusive fluctuations. Switching to corotating states is mainly driven by smaller diffusive fluctuations in the orientation, amplitude, and mean temperature of rolls, which have a positive feedback that destabilizes the counterrotating state. © 2023 American Physical Society.
Keywords: dept.phy; peer-reviewed

Measurements of the Elliptic and Triangular Azimuthal Anisotropies in Central He 3 +Au, d+Au and p+Au Collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2023)
The elliptic (v2) and triangular (v3) azimuthal anisotropy coefficients in central He3+Au, d+Au, and p+Au collisions at sNN=200 GeV are measured as a function of transverse momentum (pT) at midrapidity (|η|<0.9), via the azimuthal angular correlation between two particles both at |η|<0.9. While the v2(pT) values depend on the colliding systems, the v3(pT) values are system independent within the uncertainties, suggesting an influence on eccentricity from subnucleonic fluctuations in these small-sized systems. These results also provide stringent constraints for the hydrodynamic modeling of these systems. © 2023 American Physical Society.
Keywords: dept.phy; peer-reviewed

Measurement of electrons from open heavy-flavor hadron decays in Au+Au collisions at √sNN = 200 GeV with the STAR detector - STAR Collaboration (Journal of High Energy Physics, 2023)
We report a new measurement of the production of electrons from open heavy-flavor hadron decays (HFEs) at mid-rapidity (|y| < 0.7) in Au+Au collisions at sNN = 200 GeV. Invariant yields of HFEs are measured for the transverse momentum range of 3.5 < p T < 9 GeV/c in various configurations of the collision geometry. The HFE yields in head-on Au+Au collisions are suppressed by approximately a factor of 2 compared to that in p + p collisions scaled by the average number of binary collisions, indicating strong interactions between heavy quarks and the hot and dense medium created in heavy-ion collisions. Comparison of these results with models provides additional tests of theoretical calculations of heavy quark energy loss in the quark-gluon plasma. [Figure not available: see fulltext.] © 2023, The Author(s).
Keywords: Heavy Ion Experiments; Heavy Quark Production; Heavy-Ion Collision; dept.phy; peer-reviewed

Nanotechnology for Electronics, Photonics, Biosensors, and Emerging Technologies - Jain, F.; Broadbridge, C. C.; Gherasimova, M.; Tang, H.; Connecticut Microelectronics and Optoelectronics Consortium New Haven, Conn) (Selected topics in electronics and systems, 64, 2021)
Keywords: Congresses; Congresses; Biosensors; Congresses; Nanoelectronics; Congresses; Nanophotonics; Congresses; Optoelectronics; Nanotechnology; dept.phy; faculty_collection

Star-image Centering with Deep Learning: HST/WFPC2 Images - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Baena-Gallé, Roberto; Martone, Max; Schwendemann, Kate (Publications of the Astronomical Society of the Pacific, 2023)
A deep learning (DL) algorithm is built and tested for its ability to determine centers of star images in HST/WFPC2 exposures, in filters F555W and F814W. These archival observations hold great potential for proper-motion studies, but the undersampling in the camera’s detectors presents challenges for conventional centering algorithms. Two exquisite data sets of over 600 exposures of the cluster NGC 104 in these filters are used as a testbed for training and evaluating the DL code. Results indicate a single-measurement standard error from 8.5 to 11 mpix, depending on the detector and filter. This compares favorably to the ∼20 mpix achieved with the customary “effective point spread function (PSF)” centering procedure for WFPC2 images. Importantly, the pixel-phase error is largely eliminated when using the DL method. The current tests are limited to the central portion of each detector; in future studies, the DL code will be modified to allow for the known variation of the PSF across the detectors.
Keywords: dept.phy

TFAW survey II: Six newly validated planets and 13 planet candidates from K2 - Del Ser, D.; Fors, O.; Del Alcázar, M.; Dyachenko, V.; Horch, E.P.; Tokovinin, A.; Ziegler, C.; Van Belle, G.T.; Clark, C.A.; Hartman, Z.D. (Monthly Notices of the Royal Astronomical Society, 2023)
Searching for Earth-sized planets in data from Kepler's extended mission (K2) is a niche that still remains to be fully exploited. The TFAW survey is an ongoing project that aims to re-analyse all light curves in K2 C1-C8 and C12-C18 campaigns with a wavelet-based detrending and denoising method, and the period search algorithm TLS to search for new transit candidates not detected in previous works. We have analysed a first subset of 24 candidate planetary systems around relatively faint host stars (10.9 < Kp < 15.4) to allow for follow-up speckle imaging observations. Using vespa and TRICERATOPS, we statistically validate six candidates orbiting four unique host stars by obtaining false-positive probabilities smaller than 1 per cent with both methods. We also present 13 vetted planet candidates that might benefit from other, more precise follow-up observations. All of these planets are sub-Neptune-sized with two validated planets and three candidates with sub-Earth sizes, and have orbital periods between 0.81 and 23.98 d. Some interesting systems include two ultra-short-period planets, three multiplanetary systems, three sub-Neptunes that appear to be within the small planet Radius Gap, and two validated and one candidate sub-Earths (EPIC 210706310.01, K2-411 b, and K2-413 b) orbiting metal-poor stars. © 2022 The Author(s) Published by Oxford University Press on behalf of Royal Astronomical Society.
Keywords: dept.phy; instrumentation: high angular resolution; methods: data analysis; peer-reviewed; planets and satellites: general; planets and satellites: terrestrial planets; techniques: photometric

A handheld visible resonance raman analyzer used in intraoperative detection of human glioma - Zhang, Liang; Zhou, Yan; Wu, Binlin; Zhang, Shengjia; Zhu, Ke; Liu, Cheng-Hui; Yu, Xinguang; Alfano, Robert R. (Cancers, 2023)
There is still a lack of reliable intraoperative tools for glioma diagnosis and to guide the maximal safe resection of glioma. We report continuing work on the optical biopsy method to detect glioma grades and assess glioma boundaries intraoperatively using the VRR-LRRTM Raman analyzer, which is based on the visible resonance Raman spectroscopy (VRR) technique. A total of 2220 VRR spectra were collected during surgeries from 63 unprocessed fresh glioma tissues using the VRR-LRRTM Raman analyzer. After the VRR spectral analysis, we found differences in the native molecules in the fingerprint region and in the high-wavenumber region, and differences between normal (control) and different grades of glioma tissues. A principal component analysis–support vector machine (PCA-SVM) machine learning method was used to distinguish glioma tissues from normal tissues and different glioma grades. The accuracy in identifying glioma from normal tissue was over 80%, compared with the gold standard of histopathology reports of glioma. The VRR-LRRTM Raman analyzer may be a new label-free, real-time optical molecular pathology tool aiding in the intraoperative detection of glioma and identification of tumor boundaries, thus helping to guide maximal safe glioma removal and adjacent healthy tissue preservation.
Keywords: dept.phy; glioma; human brain; intraoperative; optical biopsy; optical molecular pathology; peer-reviewed; portable optical-fiber-probe Raman analyzer; visible resonance Raman (VRR)

Azimuthal anisotropy measurement of (multi)strange hadrons in Au+Au collisions at sNN =54.4 GeV - STAR Collaboration (Physical Review C, 2023)
Azimuthal anisotropy of produced particles is one of the most important observables used to access the collective properties of the expanding medium created in relativistic heavy-ion collisions. In this paper, we present second (v2) and third (v3) order azimuthal anisotropies of KS0, φ, Λ, Ξ, and ω at midrapidity (|y|<1) in Au+Au collisions at sNN=54.4 GeV measured by the STAR detector. The v2 and v3 are measured as a function of transverse momentum and centrality. Their energy dependence is also studied. v3 is found to be more sensitive to the change in the center-of-mass energy than v2. Scaling by constituent quark number is found to hold for v2 within 10%. This observation could be evidence for the development of partonic collectivity in 54.4 GeV Au+Au collisions. Differences in v2 and v3 between baryons and antibaryons are presented, and ratios of v3/v23/2 are studied and motivated by hydrodynamical calculations. The ratio of v2 of φ mesons to that of antiprotons [v2(φ)/v2(p¯)] shows centrality dependence at low transverse momentum, presumably resulting from the larger effects from hadronic interactions on antiproton v2. © 2023 American Physical Society.
Keywords: dept.phy; peer-reviewed

Pion, kaon, and (anti)proton production in U+U collisions at sNN =193 GeV measured with the STAR detector - STAR Collaboration (Physical Review C, 2023)
We present the first measurements of transverse momentum spectra of π±, K±, p(p¯) at midrapidity (|y|<0.1) in U+U collisions at sNN= 193 GeV with the STAR detector at the Relativistic Heavy Ion Collider (RHIC). The centrality dependence of particle yields, average transverse momenta, particle ratios and kinetic freeze-out parameters are discussed. The results are compared with the published results from Au+Au collisions at sNN= 200 GeV in STAR. The results are also compared to those from A Multi-Phase Transport (ampt) model. © 2023 American Physical Society.
Keywords: dept.phy; peer-reviewed

Beam energy dependence of fifth- and sixth-order net-proton number fluctuations in Au+Au collisions at RHIC - STAR Collaboration (Physical Review Letters, 2023)
We report the beam energy and collision centrality dependence of fifth and sixth order cumulants (C5, C6) and factorial cumulants (κ5, κ6) of net-proton and proton number distributions, from center-of-mass energy (sNN) 3 GeV to 200 GeV Au+Au collisions at RHIC. Cumulant ratios of net-proton (taken as proxy for net-baryon) distributions generally follow the hierarchy expected from QCD thermodynamics, except for the case of collisions at 3 GeV. The measured values of C6/C2 for 0%-40% centrality collisions show progressively negative trend with decreasing energy, while it is positive for the lowest energy studied. These observed negative signs are consistent with QCD calculations (for baryon chemical potential, μB≤110 MeV) which contains the crossover transition range. In addition, for energies above 7.7 GeV, the measured proton κn, within uncertainties, does not support the two-component (Poisson+binomial) shape of proton number distributions that would be expected from a first-order phase transition. Taken in combination, the hyperorder proton number fluctuations suggest that the structure of QCD matter at high baryon density, μB∼750 MeV at sNN=3 GeV is starkly different from those at vanishing μB∼24 MeV at sNN=200 GeV and higher collision energies. © 2023 American Physical Society.
Keywords: dept.phy; peer-reviewed

Search for the chiral magnetic effect in Au+Au collisions at sNN=27 GeV with the STAR forward event plane detectors - STAR Collaboration (Physics Letters B, 2023)
A decisive experimental test of the Chiral Magnetic Effect (CME) is considered one of the major scientific goals at the Relativistic Heavy-Ion Collider (RHIC) towards understanding the nontrivial topological fluctuations of the Quantum Chromodynamics vacuum. In heavy-ion collisions, the CME is expected to result in a charge separation phenomenon across the reaction plane, whose strength could be strongly energy dependent. The previous CME searches have been focused on top RHIC energy collisions. In this Letter, we present a low energy search for the CME in Au+Au collisions at sNN=27 GeV. We measure elliptic flow scaled charge-dependent correlators relative to the event planes that are defined at both mid-rapidity |η|<1.0 and at forward rapidity 2.1<|η|<5.1. We compare the results based on the directed flow plane (Ψ1) at forward rapidity and the elliptic flow plane (Ψ2) at both central and forward rapidity. The CME scenario is expected to result in a larger correlation relative to Ψ1 than to Ψ2, while a flow driven background scenario would lead to a consistent result for both event planes. In 10-50% centrality, results using three different event planes are found to be consistent within experimental uncertainties, suggesting a flow driven background scenario dominating the measurement. We obtain an upper limit on the deviation from a flow driven background scenario at the 95% confidence level. This work opens up a possible road map towards future CME search with the high statistics data from the RHIC Beam Energy Scan Phase-II.
Keywords: Beam energy scan; Chiral magnetic effect; Heavy-ion collisions; dept.phy; peer-reviewed

Beam energy dependence of the linear and mode-coupled flow harmonics in Au+Au collisions - STAR Collaboration (Physics Letters B, 2023)
The linear and mode-coupled contributions to higher-order anisotropic flow are presented for Au+Au collisions at sNN = 27, 39, 54.4, and 200 GeV and compared to similar measurements for Pb+Pb collisions at the Large Hadron Collider (LHC). The coefficients and the flow harmonics' correlations, which characterize the linear and mode-coupled response to the lower-order anisotropies, indicate a beam energy dependence consistent with an influence from the specific shear viscosity (η/s). In contrast, the dimensionless coefficients, mode-coupled response coefficients, and normalized symmetric cumulants are approximately beam-energy independent, consistent with a significant role from initial-state effects. These measurements could provide unique supplemental constraints to (i) distinguish between different initial-state models and (ii) delineate the temperature (T) and baryon chemical potential (μB) dependence of the specific shear viscosity ηs(T,μB).
Keywords: Collectivity; Correlation; Shear viscosity; dept.phy; peer-reviewed

Stokes shift spectroscopy and machine learning for label-free human prostate cancer detection - Pu, Y.; Wu, B.; Mo, H.; Alfano, R.R. (Optics Letters, 2023)
The Stokes shift spectra (S3) of human cancerous and normal prostate tissues were collected label free at a selected wavelength interval of 40 nm to investigate the efficacy of the approach based on three key molecules—tryptophan, collagen, and reduced nicotinamide adenine dinucleotide (NADH)—as cancer biomarkers. S3 combines both fluorescence and absorption spectra in one scan. The S3 spectra were analyzed using machine learning (ML) algorithms, including principal component analysis (PCA), nonnegative matrix factorization (NMF), and support vector machines (SVMs). The components retrieved from the S3 spectra were considered principal biomarkers. The differences in the weights of the components between the two types of tissues were found to be significant. Sensitivity, specificity, and accuracy were calculated to evaluate the performance of SVM classification. This research demonstrates that S3 spectroscopy is effective for detecting the changes in the relative concentrations of the endogenous fluorophores in tissues due to the development of cancer label free. © 2023 Optica Publishing Group.
Keywords: dept.phy; peer-reviewed

Pattern of global spin alignment of ϕ and K*0 mesons in heavy-ion collisions - STAR Collaboration (Nature, 2023)
Notwithstanding decades of progress since Yukawa first developed a description of the force between nucleons in terms of meson exchange1, a full understanding of the strong interaction remains a considerable challenge in modern science. One remaining difficulty arises from the non-perturbative nature of the strong force, which leads to the phenomenon of quark confinement at distances on the order of the size of the proton. Here we show that, in relativistic heavy-ion collisions, in which quarks and gluons are set free over an extended volume, two species of produced vector (spin-1) mesons, namely ϕ and K*0, emerge with a surprising pattern of global spin alignment. In particular, the global spin alignment for ϕ is unexpectedly large, whereas that for K*0 is consistent with zero. The observed spin-alignment pattern and magnitude for ϕ cannot be explained by conventional mechanisms, whereas a model with a connection to strong force fields2–6, that is, an effective proxy description within the standard model and quantum chromodynamics, accommodates the current data. This connection, if fully established, will open a potential new avenue for studying the behaviour of strong force fields. © 2023, The Author(s), under exclusive licence to Springer Nature Limited.
Keywords: dept.phy; peer-reviewed

Waste Citrus reticulata Assisted Preparation of Cobalt Oxide Nanoparticles for Supercapacitors - Srivastava, Rishabh; Bhardwaj, Shiva; Kumar, Anuj; Singhal, Rahul; Scanley, Jules; Broadbridge, Christine C.; Gupta, Ram K. (Nanomaterials, 2022)
The green, sustainable, and inexpensive creation of novel materials, primarily nanoparticles, with effective energy-storing properties, is key to addressing both the rising demand for energy storage and the mounting environmental concerns throughout the world. Here, an orange peel extract is used to make cobalt oxide nanoparticles from cobalt nitrate hexahydrate. The orange peel extract has Citrus reticulata, which is a key biological component that acts as a ligand and a reducing agent during the formation of nanoparticles. Additionally, the same nanoparticles were also obtained from various precursors for phase and electrochemical behavior comparisons. The prepared Co-nanoparticles were also sulfurized and phosphorized to enhance the electrochemical properties. The synthesized samples were characterized using scanning electron microscopic and X-ray diffraction techniques. The cobalt oxide nanoparticle showed a specific capacitance of 90 F/g at 1 A/g, whereas the cobalt sulfide and phosphide samples delivered an improved specific capacitance of 98 F/g and 185 F/g at 1 A/g. The phosphide-based nanoparticles offer more than 85% capacitance retention after 5000 cycles. This study offers a green strategy to prepare nanostructured materials for energy applications.
Keywords: Citrus reticulata; Co3O4 nanoparticles; characterization; charge storage; dept.phy; peer-reviewed; supercapacitors

Chapter 15 - Tryptophan fluorescence and machine learning to study the aggressiveness of prostate cancer cell lines: A pilot study - Xue, Jianpeng; Mo, Haiding; Tian, Yuke; Tang, Rui; Wu, Binlin (Biophotonics, Tryptophan and Disease, 2022)
We report on the use of label-free, native fluorescence (NFL) spectroscopy and machine learning (ML) algorithms to study the correlation of relative tryptophan levels with prostate cancer aggressiveness. Three extensively studied prostate cancer cell lines were used; PC3, an aggressive, androgen-resistant line, with a high tendency to metastasize in vivo, DU-145, a less aggressive cancer cell line, also androgen-resistant, and LNCaP, an androgen sensitive line, which has a low tendency to metastasize. Using an excitation of 300nm, differences in the NFL spectral profiles from these cell lines were found to correlate with changes in the relative concentrations of tryptophan and reduced nicotinamide adenine dinucleotide (NADH). The use of ML may present a powerful tool for the assessment of the likelihood of a cancer to metastasize. This technique could aid in the decision whether to use highly aggressive adjuvant chemotherapy or radiation therapy after surgical resection of a prostate cancer.
Keywords: Fluorescence spectroscopy; Machine learning; Metastatic cancer; Native fluorescence; Prostate cancer; Support vector machine; Tryptophan; dept.phy

The Solar Neighborhood L: Spectroscopic Discovery of K Dwarfs Younger Than 1 Gyr and New Binaries within 30 pc - Hubbard-James, Hodari-Sadiki; Lesley, D. Xavier; Henry, Todd J.; Paredes, Leonardo A.; Nisak, Azmain H. (The Astronomical Journal, 2022)
As part of a comprehensive effort to characterize the nearest stars, the CHIRON echelle spectrograph on the CTIO/SMARTS 1.5 m telescope is being used to acquire high-resolution (R = 80,000) spectra of K dwarfs within 50 pc. This paper provides spectral details about 35 K dwarfs from five benchmark sets with estimated ages spanning 20 Myr–5.7 Gyr. Four spectral age and activity indicators are tested, three of which aligned with the estimated ages of the benchmark groups—the Na i doublet (5889.95 and 5895.92 Å), the Hα line (6562.8 Å), and the Li i resonance line (6707.8 Å). The benchmark stars are then used to evaluate seven field K dwarfs exhibiting variable radial velocities for which initial CHIRON data did not show obvious companions. Two of these stars are estimated to be younger than 700 Myr, while one exhibits stellar activity unusual for older K-dwarf field stars and is possibly young. The four remaining stars turn out to be spectroscopic binaries, two of which are being reported here for the first time with orbital periods found using CHIRON data. Spectral analysis of the combined sample of 42 benchmark and variable radial velocity stars indicates temperatures ranging from 3900 to 5300 K and metallicities from −0.4 < [Fe/H] < +0.2. We also determine for main-sequence K dwarfs. Ultimately, this study will target several thousand of the nearest K dwarfs and provide results that will serve present and future studies of stellar astrophysics and exoplanet habitability.
Keywords: dept.phy; peer-reviewed

Measurement of HΛ4 and HeΛ4 binding energy in Au+Au collisions at sNN = 3 GeV - STAR Collaboration (Physics Letters B, 2022)
Measurements of mass and Λ binding energy of Λ4H and Λ4He in Au+Au collisions at sNN=3 GeV are presented, with an aim to address the charge symmetry breaking (CSB) problem in hypernuclei systems with atomic number A = 4. The Λ binding energies are measured to be 2.22±0.06(stat.)±0.14(syst.) MeV and 2.38±0.13(stat.)±0.12(syst.) MeV for Λ4H and Λ4He, respectively. The measured Λ binding-energy difference is 0.16±0.14(stat.)±0.10(syst.) MeV for ground states. Combined with the γ-ray transition energies, the binding-energy difference for excited states is −0.16±0.14(stat.)±0.10(syst.) MeV, which is negative and comparable to the value of the ground states within uncertainties. These new measurements on the Λ binding-energy difference in A = 4 hypernuclei systems are consistent with the theoretical calculations that result in ΔBΛ4(1exc+)≈−ΔBΛ4(0g.s.+)<0 and present a new method for the study of CSB effect using relativistic heavy-ion collisions.
Keywords: dept.phy; peer-reviewed

Resolving the Core of R136 in the Optical - Kalari, V.M.; Horch, E.P.; Salinas, R.; Vink, J.S.; Andersen, M.; Bestenlehner, J.M.; Rubio, M. (Astrophysical Journal, 2022)
The sharpest optical images of the R136 cluster in the Large Magellanic Cloud are presented, allowing us for the first time to resolve members of the central core, including R136a1, the most-massive star known. These data were taken using the Gemini speckle imager Zorro in medium-band filters with effective wavelengths similar to BVRI achieving angular resolutions between 30-40 mas. All stars previously known in the literature, having V < 16 mag within the central 2″ × 2″, were recovered. Visual companions (≥40 mas; 2000 au) were detected for the WN5h stars R136 a1 and a3. Photometry of the visual companion of a1 suggests it is of mid-O spectral type. Based on new photometric luminosities using the resolved Zorro imaging, the masses of the individual WN5h stars are estimated to be between 150 and 200 M ⊙, lowering significantly the present-day masses of some of the most-massive stars known. These mass estimates are critical anchor points for establishing the stellar upper-mass function. © 2022. The Author(s). Published by the American Astronomical Society.
Keywords: dept.phy; peer-reviewed

Centrality and transverse-momentum dependence of higher-order flow harmonics of identified hadrons in Au+Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2022)
We present high-precision measurements of elliptic, triangular, and quadrangular flow v2, v3, and v4, respectively, at midrapidity for identified hadrons π, p, K, φ, Ks, Λ as a function of centrality and transverse momentum in Au+Au collisions at the center-of-mass energy sNN=200 GeV. We observe similar vn trends between light and strange mesons which indicates that the heavier strange quarks flow as strongly as the lighter up and down quarks. The number-of-constituent-quark scaling for v2, v3, and v4 is found to hold within statistical uncertainty for 0-10%, 10-40%, and 40-80% collision centrality intervals. The results are compared to several viscous hydrodynamic calculations with varying initial conditions, and could serve as an additional constraint to the development of hydrodynamic models. © 2022 American Physical Society.
Keywords: dept.phy; peer-reviewed

The POKEMON Speckle Survey of Nearby M Dwarfs. I. New Discoveries - Clark, C.A.; Van Belle, G.T.; Horch, E.P.; Von Braun, K.; Ciardi, D.R.; Winters, J.G.; Kiman, R. (Astronomical Journal, 2022)
M dwarfs are favorable targets for exoplanet detection with current instrumentation, but stellar companions can induce false positives and inhibit planet characterization. Knowledge of stellar companions is also critical to our understanding of how binary stars form and evolve. We have therefore conducted a survey of stellar companions around nearby M dwarfs, and here we present our new discoveries. Using the Differential Speckle Survey Instrument at the 4.3 m Lowell Discovery Telescope, and the similar NN-EXPLORE Exoplanet Stellar Speckle Imager at the 3.5 m WIYN telescope, we carried out a volume-limited survey of M-dwarf multiplicity to 15 parsecs, with a special emphasis on including the later M dwarfs that were overlooked in previous surveys. Additional brighter targets at larger distances were included for a total sample size of 1070 M dwarfs. Observations of these 1070 targets revealed 26 new companions; 22 of these systems were previously thought to be single. If all new discoveries are confirmed, then the number of known multiples in the sample will increase by 7.6%. Using our observed properties, as well as the parallaxes and 2MASS K magnitudes for these objects, we calculate the projected separation, and estimate the mass ratio and component spectral types, for these systems. We report the discovery of a new M-dwarf companion to the white dwarf Wolf 672 A, which hosts a known M-dwarf companion as well, making the system trinary. We also examine the possibility that the new companion to 2MASS J13092185-2330350 is a brown dwarf. Finally, we discuss initial insights from the POKEMON survey. © 2022. The Author(s). Published by the American Astronomical Society.
Keywords: dept.phy; peer-reviewed

Probing strangeness canonical ensemble with K−, ϕ(1020) and Ξ− production in Au+Au collisions at sNN=3 GeV - STAR Collaboration (Physics Letters B, 2022)
We report the first multi-differential measurements of strange hadrons of K−, ϕ and Ξ− yields as well as the ratios of ϕ/K− and ϕ/Ξ− in Au+Au collisions at sNN=3 GeV with the STAR experiment fixed target configuration at RHIC. The ϕ mesons and Ξ− hyperons are measured through hadronic decay channels, ϕ→K+K− and Ξ−→Λπ−. Collision centrality and rapidity dependence of the transverse momentum spectra for these strange hadrons are presented. The 4π yields and ratios are compared to thermal model and hadronic transport model predictions. At this collision energy, thermal model with grand canonical ensemble (GCE) under-predicts the ϕ/K− and ϕ/Ξ− ratios while the result of canonical ensemble (CE) calculations reproduce ϕ/K−, with the correlation length rc∼2.7 fm, and ϕ/Ξ−, rc∼4.2 fm, for the 0-10% central collisions. Hadronic transport models including high mass resonance decays could also describe the ratios. While thermal calculations with GCE work well for strangeness production in high energy collisions, the change to CE at 3 GeV implies a rather different medium property at high baryon density.
Keywords: dept.phy; peer-reviewed

Convolutional Neural Network for Binary Classification of Chromophobe Renal Cell Carcinoma and Oncocytoma - Cheng, Andrew; Icaza, Michael; Judd, Nicholas; Smith, Jason; Mukherjee, Sushmita; Jain, Manu; Wu, Binlin (Frontiers in Optics, 2021)
Multiphoton microscopy images of chromophobe renal cell carcinoma and renal oncocytoma were classified using a convolutional neural network inspired by techniques in recent architectures and yielded over 70% accuracy.
Keywords: dept.phy

Probing the Gluonic Structure of the Deuteron with J/ψ Photoproduction in d+Au Ultraperipheral Collisions - STAR Collaboration (Physical Review Letters, 2022)
Understanding gluon density distributions and how they are modified in nuclei are among the most important goals in nuclear physics. In recent years, diffractive vector meson production measured in ultraperipheral collisions (UPCs) at heavy-ion colliders has provided a new tool for probing the gluon density. In this Letter, we report the first measurement of J/ψ photoproduction off the deuteron in UPCs at the center-of-mass energy sNN=200 GeV in d+Au collisions. The differential cross section as a function of momentum transfer -t is measured. In addition, data with a neutron tagged in the deuteron-going zero-degree calorimeter is investigated for the first time, which is found to be consistent with the expectation of incoherent diffractive scattering at low momentum transfer. Theoretical predictions based on the color glass condensate saturation model and the leading twist approximation nuclear shadowing model are compared with the data quantitatively. A better agreement with the saturation model has been observed. With the current measurement, the results are found to be directly sensitive to the gluon density distribution of the deuteron and the deuteron breakup process, which provides insights into the nuclear gluonic structure. © 2022 American Physical Society.
Keywords: dept.phy; peer-reviewed

The Solar Neighborhood. XLIX. New Discoveries and Orbits of M-dwarf Multiples with Speckle Interferometry at SOAR - Vrijmoet, E.H.; Tokovinin, A.; Henry, T.J.; Winters, J.G.; Horch, E.; Jao, W.-C. (Astronomical Journal, 2022)
We present the first results of a multiyear program to map the orbits of M-dwarf multiples within 25 pc. The observations were conducted primarily during 2019-2020 using speckle interferometry at the Southern Astrophysical Research Telescope in Chile, using the High-Resolution Camera mounted on the adaptive optics module (HRCam+SAM). The sample of nearby M dwarfs is drawn from three sources: multiples from the RECONS long-term astrometric monitoring program at the SMARTS 0.9 m; known multiples, for which these new observations will enable or improve orbit fits; and candidate multiples flagged by their astrometric fits in Gaia Data Release 2 (DR2). We surveyed 333 of our 338 M dwarfs via 830 speckle observations, detecting companions for 63% of the stars. Most notably, this includes new companions for 76% of the subset selected from Gaia DR2. In all, we report the first direct detections of 97 new stellar companions to the observed M dwarfs. Here we present the properties of those detections, the limits of each nondetection, and five orbits with periods 0.67-29 yr already observed as part of this program. Companions detected have projected separations of 0.″024-2.″0 (0.25-66 au) from their primaries and have ΔI ≲ 5.0 mag. This multiyear campaign will ultimately map complete orbits for nearby M dwarfs with periods up to 3 yr, and provide key epochs to stretch orbital determinations for binaries to 30 yr. © 2022. The Author(s). Published by the American Astronomical Society.
Keywords: dept.phy; peer-reviewed

The optomechanical design of the Quad-camera Wavefront-sensing Six-channel Speckle Interferometer (QWSSI) - Clark, C.A.; Van Belle, G.T.; Horch, E.P.; Trilling, D.E.; Hartman, Z.D.; Collins, M.; Von Braun, K.; Gehring, J. (SPIE, 2020)
The Quad-camera Wavefront-sensing Six-channel Speckle Interferometer (QWSSI) is a new speckle imaging instrument available on the 4.3-m Lowell Discovery Telescope (LDT). QWSSI is built to efficiently make use of collected photons and available detector area. The instrument images on a single Electron Multiplying CCD (EMCCD) at four wavelengths in the optical (577, 658, 808, and 880nm) with 40nm bandpasses. Longward of 1μm, two imaging wavelengths in the NIR are collected at 1150 and 1570nm on two InGaAs cameras with 50nm bandpasses. All remaining non-imaging visible light is then sent into a wavefront EMCCD. All cameras are operated synchronously via concurrent triggering from a timing module. With the simultaneous wavefront sensing, QWSSI characterizes atmospheric aberrations in the wavefront for each speckle frame. This results in additional data that can be utilized during post-processing, enabling advanced techniques such as Multi-Frame Blind Deconvolution. The design philosophy was optimized for an inexpensive, rapid build; virtually all parts were commercial-off-the-shelf (COTS), and custom parts were fabricated or 3D printed on-site. QWSSI's unique build and capabilities represent a new frontier in civilian high-resolution speckle imaging. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.
Keywords: 3D printers; Aberrations; Additional datum; Atmospheric aberration; Cameras; Commercial off-the-shelf; Convolution; Design philosophy; Diffraction-limited imaging; Gallium alloys; Gallium compounds; Indium alloys; Instrument design; Interferometers; Interferometry; Light; Multi-frame blind deconvolution; Opto-mechanical design; Optomechanics; Semiconducting indium gallium arsenide; Semiconductor alloys; Speckle; Speckle imaging; Speckle interferometer; Stellar proper- ties; Wave-front sensing; Wavefront-sensing; Wavefronts; dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2020)
Keywords: dept.phy

Toward an imaging capability with the Southern Connecticut Stellar Interferometer - Klaucke, P.M.; Pellegrino, R.A.; Weiss, S.A.; Horch, E.P. (SPIE, 2020)
The Southern Connecticut Stellar Interferometer (SCSI) is an intensity interferometer that is designed to use correlated photon arrival times to determine the geometry of stars. Originally a low-cost, two-telescope instrument that used a 1-pixel single-photon avalanche diode (SPAD) detector at the focal plane of each telescope to record photon events, it is now being upgraded to include a third telescope. This will allow for the simultaneous detection of the photon correlation at three baselines, and thus the ability to map out the two-dimensional geometry of the source much more efficiently than with the two-telescope arrangement. Recent papers in the literature suggest that it may be possible to derive phase information in the Fourier domain from such triple correlations for the brightest stars, potentially giving SCSI an imaging capability. Prior to investigating this possibility, steps must be taken to maximize the observing efficiency of the SCSI. We present here our latest efforts in achieving better pointing, tracking, and collimation with our telescopes, and we discuss our first modeling results of the three-telescope situation in order to understand under what conditions the upgraded SCSI could retrieve imaging information. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.
Keywords: Avalanche diodes; Correlation interferometry; Hanbury Brown and Twiss Effect; Image reconstruction; Imaging capabilities; Imaging information; Interferometers; Interferometry; Observing efficiency; Optical intensity interferometry; Particle beams; Phase recovery; Photons; Simultaneous detection; Single photon avalanche diode; Stars; Stellar interferometers; Telescope instruments; Telescopes; Two-dimensional geometry; dept.phy

Global Λ-hyperon polarization in Au+Au collisions at √sNN = 3 GeV - STAR Collaboration (Physical Review C, 2021)
Global hyperon polarization, P¯H, in Au+Au collisions over a large range of collision energy, sNN, was recently measured and successfully reproduced by hydrodynamic and transport models with intense fluid vorticity of the quark-gluon plasma. While naïve extrapolation of data trends suggests a large P¯H as the collision energy is reduced, the behavior of P¯H at small sNN¡7.7 GeV is unknown. Operating the STAR experiment in fixed-target mode, we measured the polarization of Λ hyperons along the direction of global angular momentum in Au+Au collisions at sNN=3 GeV. The observation of substantial polarization of 4.91±0.81(stat.)±0.15(syst.)% in these collisions may require a reexamination of the viscosity of any fluid created in the collision, of the thermalization timescale of rotational modes, and of hadronic mechanisms to produce global polarization. © 2021 American Physical Society.
Keywords: dept.phy; peer-reviewed

Measurement of the sixth-order cumulant of net-proton multiplicity distributions in au+au collisions at s NN =27, 54.4, and 200 GeV at RHIC - STAR Collaboration (Physical Review Letters, 2021)
According to first-principle lattice QCD calculations, the transition from quark-gluon plasma to hadronic matter is a smooth crossover in the region μB≤Tc. In this range the ratio, C6/C2, of net-baryon distributions are predicted to be negative. In this Letter, we report the first measurement of the midrapidity net-proton C6/C2 from 27, 54.4, and 200 GeV Au+Au collisions at the Relativistic Heavy Ion Collider (RHIC). The dependence on collision centrality and kinematic acceptance in (pT, y) are analyzed. While for 27 and 54.4 GeV collisions the C6/C2 values are close to zero within uncertainties, it is observed that for 200 GeV collisions, the C6/C2 ratio becomes progressively negative from peripheral to central collisions. Transport model calculations without critical dynamics predict mostly positive values except for the most central collisions within uncertainties. These observations seem to favor a smooth crossover in the high-energy nuclear collisions at top RHIC energy. © 2021 American Physical Society.
Keywords: Au+Au collisions; Colliding beam accelerators; Cumulants; First principles; Germanium alloys; Germanium compounds; Gold compounds; Hadronic matters; Heavy ions; Lattice QCD calculations; Measurements of; Mid-rapidity; Multiplicity distributions; Quantum theory; Quark-gluon plasma; Uncertainty; dept.phy; peer-reviewed

Understanding reentrance in frustrated magnets: The case of the Er2Sn2 O7 pyrochlore - Yahne, D.R.; Pereira, D.; Jaubert, L.D.C.; Sanjeewa, L.D.; Powell, M.; Kolis, J.W.; Xu, G.; Enjalran, M.; Gingras, M.J.P.; Ross, K.A. (Physical Review Letters, 2021)
Reentrance, the return of a system from an ordered phase to a previously encountered less-ordered one as a controlled parameter is continuously varied, is a recurring theme found in disparate physical systems, yet its microscopic cause is often not investigated thoroughly. Here, through detailed characterization and theoretical modeling, we uncover the microscopic mechanism behind reentrance in the strongly frustrated pyrochlore antiferromagnet Er2Sn2O7. We use single crystal heat capacity measurements to expose that Er2Sn2O7 exhibits multiple instances of reentrance in its magnetic field B vs temperature T phase diagram for magnetic fields along three cubic high symmetry directions. Through classical Monte Carlo simulations, mean field theory, and classical linear spin-wave expansions, we argue that the origins of the multiple occurrences of reentrance observed in Er2Sn2O7 are linked to soft modes. These soft modes arise from phase competition and enhance thermal fluctuations that entropically stabilize a specific ordered phase, resulting in an increased transition temperature for certain field values and thus the reentrant behavior. Our work represents a detailed examination into the mechanisms responsible for reentrance in a frustrated magnet and may serve as a template for the interpretation of reentrant phenomena in other physical systems. © 2021 American Physical Society.
Keywords: Antiferromagnets; Binary alloys; Controlled parameter; Crystal symmetry; Frustrated magnet; Intelligent systems; Magnetic fields; Magnetic-field; Magnetization; Magnets; Mean field theory; Microscopic mechanisms; Monte Carlo methods; Ordered phasis; Physical systems; Pyrochlores; Single crystals; Soft modes; Specific heat; Spin waves; Theoretical modeling; dept.phy

A new absolute proper motion determination of leo i using HST/WFPC2 images and gaia EDR3 - Casetti-Dinescu, D.I.; Hansen, C.K.; Girard, T.M.; Kozhurina-Platais, V.; Platais, I.; Horch, E.P. (Astronomical Journal, 2022)
We measure the absolute proper motion of Leo I using a WFPC2/HST data set that spans up to 10 yr to date the longest time baseline utilized for this satellite. The measurement relies on ∼2300 Leo I stars located near the center of light of the galaxy; the correction to absolute proper motion is based on 174 Gaia EDR3 stars and 10 galaxies. Having generated highly precise, relative proper motions for all Gaia EDR3 stars in our WFPC2 field of study, our correction to the absolute EDR3 system does not rely on these Gaia stars being Leo I members. This new determination also benefits from a recently improved astrometric calibration of WFPC2. The resulting proper-motion value, (μ α , μ δ ) = (-0.007 0.035, - 0.119 0.026) mas yr-1 is in agreement with recent, large-area, Gaia EDR3-based determinations. We discuss all the recent measurements of Leo I's proper motion and adopt a combined, multistudy average of (μ α 3 meas,μ δ 3 meas)=(-0.036±0.016,-0.130±0.010) mas yr-1. This value of absolute proper motion for Leo I indicates its orbital pole is well aligned with that of the vast polar structure, defined by the majority of the brightest dwarf spheroidal satellites of the Milky Way. © 2021. The Author(s). Published by the American Astronomical Society.
Keywords: dept.phy; peer-reviewed

Validation of 13 hot and potentially terrestrial TESS planets - Giacalone, S.; Dressing, C.D.; Hedges, C.; Kostov, V.B.; Collins, K.A.; Jensen, E.L.N.; Yahalomi, D.A.; Bieryla, A.; Ciardi, D.R.; Howell, S.B.; Lillo-Box, J.; Barkaoui, K.; et al. (Astronomical Journal, 2022)
The James Webb Space Telescope will be able to probe the atmospheres and surface properties of hot, terrestrial planets via emission spectroscopy. We identify 18 potentially terrestrial planet candidates detected by the Transiting Exoplanet Survey Satellite (TESS) that would make ideal targets for these observations. These planet candidates cover a broad range of planet radii (R p ∼0.6-2.0R ) and orbit stars of various magnitudes (K s = 5.78-10.78, V = 8.4-15.69) and effective temperatures (T eff ∼3000-6000 K). We use ground-based observations collected through the TESS Follow-up Observing Program (TFOP) and two vetting tools - DAVE and TRICERATOPS - to assess the reliabilities of these candidates as planets. We validate 13 planets: TOI-206 b, TOI-500 b, TOI-544 b, TOI-833 b, TOI-1075 b, TOI-1411 b, TOI-1442 b, TOI-1693 b, TOI-1860 b, TOI-2260 b, TOI-2411 b, TOI-2427 b, and TOI-2445 b. Seven of these planets (TOI-206 b, TOI-500 b, TOI-1075 b, TOI-1442 b, TOI-2260 b, TOI-2411 b, and TOI-2445 b) are ultra-short-period planets. TOI-1860 is the youngest (133 ± 26 Myr) solar twin with a known planet to date. TOI-2260 is a young (321 ± 96 Myr) G dwarf that is among the most metal-rich ([Fe/H] = 0.22 ± 0.06 dex) stars to host an ultra-short-period planet. With an estimated equilibrium temperature of 1/42600 K, TOI-2260 b is also the fourth hottest known planet with R p ¡ 2 R . © 2022. The Author(s). Published by the American Astronomical Society.
Keywords: dept.phy; peer-reviewed

Observations with the Southern Connecticut Stellar Interferometer. I. Instrument Description and First Results - Horch, E.P.; Weiss, S.A.; Klaucke, P.M.; Pellegrino, R.A.; Rupert, J.D. (Astronomical Journal, 2022)
We discuss the design, construction, and operation of a new intensity interferometer, based on the campus of Southern Connecticut State University in New Haven, Connecticut. While this paper will focus on observations taken with an original two-telescope configuration, the current instrumentation consists of three portable 0.6 m Dobsonian telescopes with single-photon avalanche diode detectors located at the Newtonian focus of each telescope. Photons detected at each station are time stamped and read out with timing correlators that can give cross-correlations in timing to a precision of 48 ps. We detail our observations to date with the system, which has now been successfully used at our university in 16 nights of observing. Components of the instrument were also deployed on one occasion at Lowell Observatory, where the Perkins and Hall telescopes were made to function as an intensity interferometer. We characterize the performance of the instrument in detail. In total, the observations indicate the detection of a correlation peak at the level of 6.76σ when observing unresolved stars, and consistency with partial or no detection when observing at a baseline sufficient to resolve the star. Using these measurements, we conclude that the angular diameter of Arcturus is larger than 15 mas and that of Vega is between 0.8 and 17 mas. While the uncertainties are large at this point, both results are consistent with measures from amplitude-based long baseline optical interferometers. © 2022. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; peer-reviewed

Disappearance of partonic collectivity in sNN=3 GeV au+au collisions at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2022)
We report on the measurements of directed flow v1 and elliptic flow v2 for hadrons (π±, K±, KS0, p, ϕ, Λ and Ξ−) from Au+Au collisions at sNN=3 GeV and v2 for (π±, K±, p and p‾) at 27 and 54.4 GeV with the STAR experiment. While at the two higher energy midcentral collisions the number-of-constituent-quark (NCQ) scaling holds, at 3 GeV the v2 at midrapidity is negative for all hadrons and the NCQ scaling is absent. In addition, the v1 slopes at midrapidity for almost all observed hadrons are found to be positive, implying dominant repulsive baryonic interactions. The features of negative v2 and positive v1 slope at 3 GeV can be reproduced with a baryonic mean-field in transport model calculations. These results imply that the medium in such collisions is likely characterized by baryonic interactions. © 2022 The Author(s)
Keywords: dept.phy; peer-reviewed

Light nuclei collectivity from sNN=3 GeV au+au collisions at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2022)
In high-energy heavy-ion collisions, partonic collectivity is evidenced by the constituent quark number scaling of elliptic flow anisotropy for identified hadrons. A breaking of this scaling and dominance of baryonic interactions is found for identified hadron collective flow measurements in sNN = 3 GeV Au+Au collisions. In this paper, we report measurements of the first- and second-order azimuthal anisotropic parameters, v1 and v2, of light nuclei (d, t, 3He, 4He) produced in sNN = 3 GeV Au+Au collisions at the STAR experiment. An atomic mass number scaling is found in the measured v1 slopes of light nuclei at mid-rapidity. For the measured v2 magnitude, a strong rapidity dependence is observed. Unlike v2 at higher collision energies, the v2 values at mid-rapidity for all light nuclei are negative and no scaling is observed with the atomic mass number. Calculations by the Jet AA Microscopic Transport Model (JAM), with baryonic mean-field plus nucleon coalescence, are in good agreement with our observations, implying baryonic interactions dominate the collective dynamics in 3 GeV Au+Au collisions at RHIC. © 2022 The Author
Keywords: dept.phy; peer-reviewed

Measurement of cold nuclear matter effects for inclusive J/ψ in p+Au collisions at sNN=200 GeV - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2022)
Measurement by the STAR experiment at RHIC of the cold nuclear matter (CNM) effects experienced by inclusive J/ψ at mid-rapidity in 0-100% p+Au collisions at sNN = 200 GeV is presented. Such effects are quantified utilizing the nuclear modification factor, RpAu, obtained by taking a ratio of J/ψ yield in p+Au collisions to that in p+p collisions scaled by the number of binary nucleon-nucleon collisions. The differential J/ψ yield in both p+p and p+Au collisions is measured through the dimuon decay channel, taking advantage of the trigger capability provided by the Muon Telescope Detector in the RHIC 2015 run. Consequently, the J/ψ RpAu is derived within the transverse momentum (pT) range of 0 to 10 GeV/c. A suppression of approximately 30% is observed for pT<2 GeV/c, while J/ψ RpAu becomes compatible with unity for pT greater than 3 GeV/c, indicating the J/ψ yield is minimally affected by the CNM effects at high pT. Comparison to a similar measurement from 0-20% central Au+Au collisions reveals that the observed strong J/ψ suppression above 3 GeV/c is mostly due to the hot medium effects, providing strong evidence for the formation of the quark-gluon plasma in these collisions. Several model calculations show qualitative agreement with the measured J/ψ RpAu, while their agreement with the J/ψ yields in p+p and p+Au collisions is worse. © 2022 The Author(s)
Keywords: dept.phy; peer-reviewed

Measurement of inclusive electrons from open heavy-flavor hadron decays in p+p collisions at s =200 GeV with the STAR detector - STAR Collaboration (Physical Review D, 2022)
We report a new measurement of the production cross section for inclusive electrons from open heavy-flavor hadron decays as a function of transverse momentum (pT) at midrapidity (|y|¡0.7) in p+p collisions at s=200 GeV. The result is presented for 2.5¡pT¡10 GeV/c with an improved precision above 6 GeV/c with respect to the previous measurements, providing more constraints on perturbative QCD calculations. Moreover, this measurement also provides a high-precision reference for measurements of nuclear modification factors for inclusive electrons from open-charm and -bottom hadron decays in heavy-ion collisions. © 2022 American Physical Society.
Keywords: dept.phy; peer-reviewed

A Comprehensive Astrometric Calibration of HST's WFPC2. I. Distortion Mapping - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Kozhurina-Platais, Vera; Platais, Imants; Anderson, Jay; Horch, Elliott P. (Publications of the Astronomical Society of the Pacific, 2021)
Wide field planetary camera 2 (WFPC2) exposures are already some 20 years older than Gaia epoch observations, or future James Webb Space Telescope observations. As such, they offer an unprecedented time baseline for high-precision proper-motion studies, provided the full astrometric potential of these exposures is reached. We have started such a project with the work presented here being its first step. We explore geometric distortions beyond the well-known ones published in the early 2000 s. This task is accomplished by using the entire database of WFPC2 exposures in filters F555W, F606W and F814W and three standard astrometric catalogs: Gaia EDR3, 47 Tuc and ωCen. The latter two were constructed using Hubble Space Telescope observations made with cameras other than WFPC2. We explore a suite of centering algorithms, and various distortion maps in order to understand and quantify their performance. We find no high-frequency systematics beyond the 34th-row correction, down to a resolution of 10 pixels. Low-frequency systematics starting at a resolution of 50 pixels are present at a level of 30–50 millipix (1.4–2.3 mas) for the PC and 20–30 millipix (2–3 mas) for the WF chips. We characterize these low-frequency systematics by providing correction maps and updated cubic-distortion coefficients for each filter.
Keywords: dept.mat; dept.phy; peer-reviewed

Dissecting the Quadruple Binary Hyad vA 351 Masses for Three M Dwarfs and a White Dwarf* - Benedict, G. Fritz; Franz, Otto G.; Horch, Elliott P.; Prato, L.; Torres, Guillermo; McArthur, Barbara E.; Wasserman, Lawrence H.; Latham, David W.; Stefanik, Robert P.; Latham, Christian; Skiff, Brian A. (The Astronomical Journal, 2021)
We extend results first announced by Franz et al., that identified vA 351 = H346 in the Hyades as a multiple star system containing a white dwarf. With Hubble Space Telescope Fine Guidance Sensor fringe tracking and scanning, and more recent speckle observations, all spanning 20.7 years, we establish a parallax, relative orbit, and mass fraction for two components, with a period, and total mass 2.1 . With ground-based radial velocities from the McDonald Observatory Otto Struve 2.1 m Telescope Sandiford Spectrograph, and Center for Astrophysics Digital Speedometers, spanning 37 years, we find that component B consists of BC, two M dwarf stars orbiting with a very short period ( days), having a mass ratio / = 0.95. We confirm that the total mass of the system can only be reconciled with the distance and component photometry by including a fainter, higher-mass component. The quadruple system consists of three M dwarfs (A, B, C) and one white dwarf (D). We determine individual M dwarf masses = 0.53 ± 0.10 , = 0.43 ± 0.04 , and = 0.41 ± 0.04 . The white dwarf mass, 0.54 ± 0.04 , comes from cooling models, an assumed Hyades age of 670 Myr, and consistency with all previous and derived astrometric, photometric, and radial velocity results. Velocities from Hα and He i emission lines confirm the BC period derived from absorption lines, with similar (He i) and higher (Hα) velocity amplitudes. We ascribe the larger Hα amplitude to emission from a region each component shadows from the other, depending on the line of sight.
Keywords: dept.phy; peer-reviewed

Investigation of experimental observables in search of the chiral magnetic effect in heavy-ion collisions in the STAR experiment - Choudhury, S.; Dong, X.; Drachenberg, J. L.; Dunlop, J. C.; Esumi, ShinIchi; Feng, Yicheng; Finch, E.; Hu, Yu; Jia, Jiangyong; Lauret, Jerome; Li, Wei; Liao, Jinfeng; et al. (Chinese Physics C, 2022)
The chiral magnetic effect (CME) is a novel transport phenomenon, arising from the interplay between quantum anomalies and strong magnetic fields in chiral systems. In high-energy nuclear collisions, the CME may survive the expansion of the quark-gluon plasma fireball and be detected in experiments. Over the past two decades, experimental searches for the CME have attracted extensive interest at the Relativistic Heavy Ion Collider (RHIC) and the Large Hadron Collider (LHC). The main goal of this study is to investigate three pertinent experimental approaches: the correlator, the R correlator, and the signed balance functions. We exploit simple Monte Carlo simulations and a realistic event generator (EBE-AVFD) to verify the equivalence of the core components among these methods and to ascertain their sensitivities to the CME signal and the background contributions for the isobar collisions at the RHIC. © 2022 Chinese Physical Society and the Institute of High Energy Physics of the Chinese Academy of Sciences and the Institute of Modern Physics of the Chinese Academy of Sciences and IOP Publishing Ltd.
Keywords: dept.phy; peer-reviewed

HAT-P-58b – HAT-P-64b: Seven planets transiting bright stars - Bakos, G. Á.; Hartman, Joel D.; Bhatti, Waqas; Csubry, Z.; Penev, Kaloyan; Bieryla, Allyson; Latham, D. W.; Quinn, S. N.; Buchhave, Lars A.; Kovács, Gábor L.; Torres, Guillermo; Noyes, R. W.; et al. (The Astronomical Journal, 2021)
We report the discovery and characterization of seven transiting exoplanets from the HATNet survey. The planets, which are hot Jupiters and Saturns transiting bright Sun-like stars, include: HAT-P-58b (with mass M p = 0.37 M J, radius R p = 1.33 R J, and orbital period P = 4.0138 days), HAT-P-59b (M p = 1.54 M J, R p = 1.12 R J, P = 4.1420 days), HAT-P-60b (M p = 0.57 M J, R p = 1.63 R J, P = 4.7948 days), HAT-P-61b (M p = 1.06 M J, R p = 0.90 R J, P = 1.9023 days), HAT-P-62b (M p = 0.76 M J, R p = 1.07 R J, P = 2.6453 days), HAT-P-63b (M p = 0.61 M J, R p = 1.12 R J, P = 3.3777 days), and HAT-P-64b (M p = 0.58 M J, R p = 1.70 R J, P = 4.0072 days). The typical errors on these quantities are 0.06 M J, 0.03 R J, and 0.2 s, respectively. We also provide accurate stellar parameters for each of the host stars. With V = 9.710 0.050 mag, HAT-P-60 is an especially bright transiting planet host, and an excellent target for additional follow-up observations. With R p = 1.703 0.070 R J, HAT-P-64b is a highly inflated hot Jupiter around a star nearing the end of its main-sequence lifetime, and is among the largest known planets. Five of the seven systems have long-cadence observations by TESS which are included in the analysis. Of particular note is HAT-P-59 (TOI-1826.01) which is within the northern continuous viewing zone of the TESS mission, and HAT-P-60, which is the TESS candidate TOI-1580.01. © 2021. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed

Observations with the differential speckle survey instrument. X. Preliminary orbits of k-dwarf binaries and other stars - Horch, Elliott P.; Broderick, Kyle G.; Casetti-Dinescu, Dana I.; Henry, Todd J.; Fekel, Francis C.; Muterspaugh, Matthew W.; Willmarth, Daryl W.; Winters, Jennifer G.; van Belle, Gerard T.; Clark, Catherine; Everett, Mark E. (The Astronomical Journal, 2021)
This paper details speckle observations of binary stars taken at the Lowell Discovery Telescope, the WIYN telescope, and the Gemini telescopes between 2016 January and 2019 September. The observations taken at Gemini and Lowell were done with the Differential Speckle Survey Instrument (DSSI), and those done at WIYN were taken with the successor instrument to DSSI at that site, the NN-EXPLORE Exoplanet Star and Speckle Imager (NESSI). In total, we present 378 observations of 178 systems, and we show that the uncertainty in the measurement precision for the combined data set is ∼2 mas in separation, ∼1°-2° in position angle depending on the separation, and ∼0.1 mag in magnitude difference. Together with data already in the literature, these new results permit 25 visual orbits and one spectroscopic-visual orbit to be calculated for the first time. In the case of the spectroscopic-visual analysis, which is done on the ternary star HD 173093, we calculate masses with a precision of better than 1% for all three stars in that system. Twenty-one of the visual orbits calculated have a K dwarf as the primary star; we add these to the known orbits of K-dwarf primary stars and discuss the basic orbital properties of these stars at this stage. Although incomplete, the data that exist so far indicate that binaries with K-dwarf primaries tend not to have low-eccentricity orbits at separations of one to a few tens of astronomical units, that is, on solar system scales. © 2021 Institute of Physics Publishing. All rights reserved.
Keywords: dept.phy; peer-reviewed

Global polarization of ξ and ω hyperons in au+au collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2021)
Global polarization of Ξ and ω hyperons has been measured for the first time in Au+Au collisions at sNN=200 GeV. The measurements of the Ξ- and Ξ¯+ hyperon polarization have been performed by two independent methods, via analysis of the angular distribution of the daughter particles in the parity violating weak decay Ξ→Λ+π, as well as by measuring the polarization of the daughter Λ hyperon, polarized via polarization transfer from its parent. The polarization, obtained by combining the results from the two methods and averaged over Ξ- and Ξ¯+, is measured to be ⟨PΞ ©=0.47±0.10(stat)±0.23(syst)% for the collision centrality 20%-80%. The ⟨PΞ. © 2021 American Physical Society. All rights reserved.
Keywords: Angular distribution; Au+Au collisions; Colliding beam accelerators; Global polarizations; Hyperon polarization; Measurements of; Polarization; Polarization transfer; dept.phy; peer-reviewed

Measurement of e+e- momentum and angular distributions from linearly polarized photon collisions - STAR Collaboration (Physical Review Letters, 2021)
The Breit-Wheeler process which produces matter and antimatter from photon collisions is experimentally investigated through the observation of 6085 exclusive electron-positron pairs in ultraperipheral Au+Au collisions at sqrt[s_{NN}]=200 GeV. The measurements reveal a large fourth-order angular modulation of cos4DELTAphi=(16.8+/-2.5)% and smooth invariant mass distribution absent of vector mesons (phi, omega, and rho) at the experimental limit of <=0.2% of the observed yields. The differential cross section as a function of e^{+}e^{-} pair transverse momentum P_{} peaks at low value with sqrt[ ]=38.1+/-0.9 MeV and displays a significant centrality dependence. These features are consistent with QED calculations for the collision of linearly polarized photons quantized from the extremely strong electromagnetic fields generated by the highly charged Au nuclei at ultrarelativistic speed. The experimental results have implications for vacuum birefringence and for mapping the magnetic field which is important for emergent QCD phenomena.
Keywords: Angular distribution; Angular-modulation; Au+Au collisions; Colliding beam accelerators; Differential cross section; Electron-positron pairs; Invariant mass distribution; Linearly polarized; Matter and antimatters; Photons; Transverse momenta; dept.phy; peer-reviewed

Observation of Ds± /D0 enhancement in au+au collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2021)
We report on the first measurement of charm-strange meson Ds± production at midrapidity in Au+Au collisions at sNN=200 GeV from the STAR experiment. The yield ratio between strange (Ds±) and nonstrange (D0) open-charm mesons is presented and compared to model calculations. A significant enhancement, relative to a pythia simulation of p+p collisions, is observed in the Ds±/D0 yield ratio in Au+Au collisions over a large range of collision centralities. Model calculations incorporating abundant strange-quark production in the quark-gluon plasma and coalescence hadronization qualitatively reproduce the data. The transverse-momentum integrated yield ratio of Ds±/D0 at midrapidity is consistent with a prediction from a statistical hadronization model with the parameters constrained by the yields of light and strange hadrons measured at the same collision energy. These results suggest that the coalescence of charm quarks with strange quarks in the quark-gluon plasma plays an important role in Ds±-meson production in heavy-ion collisions. © 2021 authors. Published by the American Physical Society. Funded by SCOAP3.
Keywords: Au+Au collisions; Bosons; Coalescence; Colliding beam accelerators; Collision energies; Collisional plasmas; Germanium compounds; Gold compounds; Hadrons; Heavy ion collision; Heavy ions; Meson production; Model calculations; Quantum theory; Quark production; Quark-gluon plasma; Transverse momenta; dept.phy; peer-reviewed

Nonmonotonic energy dependence of net-proton number fluctuations - STAR Collaboration (Physical Review Letters, 2021)
Nonmonotonic variation with collision energy (sNN) of the moments of the net-baryon number distribution in heavy-ion collisions, related to the correlation length and the susceptibilities of the system, is suggested as a signature for the quantum chromodynamics critical point. We report the first evidence of a nonmonotonic variation in the kurtosis times variance of the net-proton number (proxy for net-baryon number) distribution as a function of sNN with 3.1 σ significance for head-on (central) gold-on-gold (Au+Au) collisions measured solenoidal tracker at Relativistic Heavy Ion Collider. Data in noncentral Au+Au collisions and models of heavy-ion collisions without a critical point show a monotonic variation as a function of sNN. © 2021 American Physical Society.
Keywords: Colliding beam accelerators; Collision energies; Correlation lengths; Gold; Hadrons; Heavy ion collision; Heavy ions; Ion sources; Monotonic variations; Non-monotonic variation; Number fluctuations; Quantum chromodynamics; Quantum theory; Relativistic Heavy Ion Collider; dept.phy; peer-reviewed

Analysis of Stokes shift spectra for distinguishing human prostate cancerous and normal tissues using machine learning methods - Mo, Haiding; Wang, Eric; Tian, Yuke; Pu, Yang; Wu, Binlin; Alfano, Robert R. (SPIE, 2021)
Early detection of prostate cancer is critical for the success of cancer therapy. It is believed that the biochemical changes that cause the optical spectra changes would appear earlier than the histological aberration. The aim of this ex vivo study was to evaluate the ability of Stokes Shift Spectra (S3) to identify human prostate cancerous tissues from the normal. Fifteen (15) pairs of with pathologically confirmed human prostate cancerous and normal tissues underwent Stokes Shift Spectra measurements with selective wavelength interval of 40 nm. The spectra were then analyzed using machine learning (ML) algorithms to classify the two types of tissues. The ML algorithms including principal component analysis (PCA) and nonnegative matrix factorization (NMF) were used for dimension reduction and feature detection. The characteristic component spectra were used to identify the key fluorophores related to carcinogenesis. The results show that these key fluorophores within tissue, e.g., tryptophan, collagen, and NADH, have different relative concentrations between cancerous and normal tissues. A multi-class classification was performed using support vector machines (SVMs). A leave-one-out cross validation was used to evaluate the performance of the classification with the gold standard histopathological results as the ground truth. The results with high sensitivity and specificity indicate that the S3 method is effective for detecting changes of fluorophore composition in human prostate tissues due to the development of cancer. © 2021 SPIE.
Keywords: Amino acids; Diagnosis; Dimension reduction; Diseases; Factorization; Fluorophores; Histology; Learning systems; Leave-one-out cross validations; Machine learning methods; Matrix algebra; Multi-class classification; Nonnegative matrix factorization; Relative concentration; Spectra measurements; Statistical methods; Support vector machine (SVMs); Support vector machines; Tissue; Tissue engineering; Urology; dept.phy

Speckle imaging characterization of radial velocity exoplanet systems - Dalba, Paul A.; Kane, Stephen R.; Howell, Steve B; Horch, Elliott P; Li, Zhexing; Hirsch, Lea A.; Burt, Jennifer; Brandt, Timothy D.; Močnik, Teo; Henry, Gregory W. (Astronomical Journal, 2021)
We conducted speckle imaging observations of 53 stellar systems that were members of long-term radial velocity (RV) monitoring campaigns and exhibited substantial accelerations indicative of planetary or stellar companions in wide orbits. Our observations were made with blue and red filters using the Differential Speckle Survey Instrument at Gemini-South and the NN-Explore Exoplanet Stellar Speckle Imager at the WIYN telescope. The speckle imaging identifies eight luminous companions within 2" of the primary stars. In three of these systems-HD 1388, HD 87359, and HD 104304-the properties of the imaged companion are consistent with the RV measurements, suggesting that these companions may be associated with the primary and the cause of the RV variation. For all 53 stellar systems, we derive differential magnitude limits (i.e., contrast curves) from the imaging. We extend this analysis to include upper limits on companion mass in systems without imaging detections. In 25 systems, we rule out companions with masses greater than 0.2 M⊙, suggesting that the observed RV signals are caused by late-M dwarfs or substellar (potentially planetary) objects. On the other hand, the joint RV and imaging analysis almost entirely rules out planetary explanations of the RV signal for HD 19522 and suggests that the companion must have an angular separation below a few tenths of an arcsecond. This work highlights the importance of combined RV and imaging observations for characterizing the outer regions of nearby planetary systems. © 2021 Institute of Physics Publishing. All rights reserved.
Keywords: dept.phy; peer-reviewed

Speckle observations of TESS exoplanet host stars: Understanding the binary exoplanet host star orbital period distribution - Howell, Steve B; Matson, Rachel A.; Ciardi, David R; Everett, Mark E; Livingston, John H.; Scott, Nicholas J; Horch, Elliott P; Winn, Joshua N (Astronomical Journal, 2021)
We present high-resolution speckle interferometric imaging observations of TESS exoplanet host stars using the NN-EXPLORE Exoplanet and Stellar Speckle Imager instrument at the 3.5 m WIYN telescope. Eight TESS objects of interest that were originally discovered by Kepler were previously observed using the Differential Speckle Survey Instrument. Speckle observations of 186 TESS stars were carried out, and 45 (24%) likely bound companions were detected. This is approximately the number of companions we would expect to observe given the established 46% binarity rate in exoplanet host stars. For the detected binaries, the distribution of stellar mass ratio is consistent with that of the standard Raghavan distribution and may show a decrease in high-q systems as the binary separation increases. The distribution of binary orbital periods, however, is not consistent with the standard Ragahavan model, and our observations support the premise that exoplanet-hosting stars with binary companions have, in general, wider orbital separations than field binaries. We find that exoplanet-hosting binary star systems show a distribution peaking near 100 au, higher than the 40–50 au peak that is observed for field binaries. This fact led to earlier suggestions that planet formation is suppressed in close binaries.
Keywords: dept.phy; peer-reviewed

Visual Orbits of Spectroscopic Binaries with the CHARA Array. III. HD 8374 and HD 24546 - Lester, Kathryn V.; Fekel, Francis C.; Muterspaugh, Matthew; Gies, Douglas R.; Schaefer, Gail H.; Farrington, Christopher D.; Guo, Zhao; Matson, Rachel A.; Monnier, John D.; Brummelaar, Theo ten; Sturmann, Judit; Weiss, Samuel A. (The Astronomical Journal, 2020)
We present the visual orbits of two long-period spectroscopic binary stars, HD 8374 and HD 24546, using interferometric observations acquired with the CHARA Array and the Palomar Testbed Interferometer. We also obtained new radial velocities from echelle spectra using the APO 3.5 m and Fairborn 2.0 m telescopes. By combining the visual and spectroscopic observations, we solve for the full, three-dimensional orbits and determine the stellar masses and distances to within 3% uncertainty. We then estimate the effective temperature and radius of each component star through Doppler tomography and spectral energy distribution analyses, in order to compare the observed stellar parameters to the predictions of stellar evolution models. For HD 8374, we find masses of M 1 = 1.636 ± 0.050M ⊙ and M 2 = 1.587 ± 0.049M ⊙, radii of R 1 = 1.84 ± 0.05R ⊙ and R 2 = 1.66 ± 0.12R ⊙, temperatures of K and K, and an estimated age of 1.0 Gyr. For HD 24546, we find masses of M 1 = 1.434 ± 0.014M ⊙ and M 2 = 1.409 ± 0.014M ⊙, radii of R 1 = 1.67 ± 0.06R ⊙ and R 2 = 1.60 ± 0.10R ⊙, temperatures of K and K, and an estimated age of 1.4 Gyr. HD 24546 is therefore too old to be a member of the Hyades cluster, despite its physical proximity to the group.
Keywords: dept.phy; peer-reviewed

Measurement of the mass difference and the binding energy of the hypertriton and antihypertriton - STAR Collaboration (Nature Physics, 2020)
According to the CPT theorem, which states that the combined operation of charge conjugation, parity transformation and time reversal must be conserved, particles and their antiparticles should have the same mass and lifetime but opposite charge and magnetic moment. Here, we test CPT symmetry in a nucleus containing a strange quark, more specifically in the hypertriton. This hypernucleus is the lightest one yet discovered and consists of a proton, a neutron and a Λ hyperon. With data recorded by the STAR detector1–3 at the Relativistic Heavy Ion Collider, we measure the Λ hyperon binding energy BΛ for the hypertriton, and find that it differs from the widely used value4 and from predictions5–8, where the hypertriton is treated as a weakly bound system. Our results place stringent constraints on the hyperon–nucleon interaction9,10 and have implications for understanding neutron star interiors, where strange matter may be present11. A precise comparison of the masses of the hypertriton and the antihypertriton allows us to test CPT symmetry in a nucleus with strangeness, and we observe no deviation from the expected exact symmetry.
Keywords: Binding energy; Charge conjugation; Colliding beam accelerators; Combined operations; Cpt symmetries; Heavy ions; Magnetic moments; Mass difference; Opposite charge; Relativistic Heavy Ion Collider; Stars; Stringent constraints; Time reversal; dept.phy; peer-reviewed

Human glioma tumors detection by a portable visible resonance Raman analyzer with a hand-held optical fiber probe - Zhou, Yan; Zhang, Shengjia; Wu, Binlin; Yu, Xinguang; Cheng, Gangge; Zhu, Ke; Zhao, Mingyue; Zheng, Jichun; Zhang, Liang; Zhang, Mingqian; Liang, Qijun; Go, Yun Ii; et al. (Biomedical Vibrational Spectroscopy 2020: Advances in Research and Industry, 2020)
Based on Visible Resonance Raman (VRR) method, we have developed a novel label-free portable VRR LRR2000 Raman analyzer with a portable fiber-optic probe and used it for the classification of human gliomas ex vivo and for the analysis of changes in tumor chemical compositions in molecular level. The purpose of this study was to examine the performance of the LRR2000 Raman analyzer as an optical biopsy tool for detecting human brain tumors compared to the commercial laboratory HR800 and WITec300 micro confocal Raman spectroscopy instruments. As of 2018, a total 1,938 VRR spectra were collected using LRR2000, HR800 and WITec300 Raman system, ex vivo. Identification of the four grades of glioma tumors and control tissues was performed based on the characteristic native molecular fingerprints. LRR2000 demonstrated consistent diagnostic results with HR800 and WITec300 Raman systems. LRR2000 showed the advantages of high speed, convenience and low cost compared to the two confocal micro Raman systems. Using artificial intelligence (AI)-based analysis of part of the data, the cross-validated accuracy for identifying glioma tumors is ~90% compared with gold standard histopathology examination.
Keywords: Biopsy; Brain; Chemical analysis; Handhelds; Histology; Human brain; Industrial research; Molecular biology; Optical biopsies; Optical fibers; Optical molecular Pathology; Palmprint recognition; Principal component analysis; Principle component analysis; Probes; Resonance; Resonance Raman; Spectroscopy; Spectrum analysis; Support vector machines; Tissue engineering; Tumors; Vibrational spectroscopy; dept.phy; glioma tumor; handheld LRR2000 analyzer; human brain tissues; optical biopsy; principle component analysis(PCA); support vector machine (SVM); visible resonance Raman (VRR)

Measurement of inclusive J/ψ polarization in p+p collisions at s =200 GeV by the STAR experiment - STAR Collaboration (Physical Review D, 2020)
We report on new measurements of inclusive J/ψ polarization at midrapidity in p+p collisions at √s=200 GeV by the STAR experiment at the Relativistic Heavy Ion Collider. The polarization parameters, λθ, λϕ, and λθϕ, are measured as a function of transverse momentum (pT) in both the helicity and Collins-Soper (CS) reference frames within pT<10 GeV/c. Except for λθ in the CS frame at the highest measured pT, all three polarization parameters are consistent with 0 in both reference frames without any strong pT dependence. Several model calculations are compared with data, and the one using the Color Glass Condensate effective field theory coupled with nonrelativistic QCD gives the best overall description of the experimental results, even though other models cannot be ruled out due to experimental uncertainties.
Keywords: dept.phy; peer-reviewed

Beam energy dependence of net- Λ fluctuations measured by the STAR experiment at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2020)
The measurements of particle multiplicity distributions have generated considerable interest in understanding the fluctuations of conserved quantum numbers in the quantum chromodynamics (QCD) hadronization regime, in particular near a possible critical point and near the chemical freeze-out. Net-protons and net-kaons have been used as proxies for the net-baryon number and net-strangeness, respectively. We report the measurement of efficiency- and centrality-bin width-corrected cumulant ratios (C2/C1, C3/C2) of net-Λ distributions, in the context of both strangeness and baryon number conservation, as a function of collision energy, centrality, and rapidity. The results are for Au+Au collisions at five beam energies (√sNN=19.6, 27, 39, 62.4, and 200 GeV) recorded with the Solenoidal Tracker at RHIC (STAR). We compare our results to the Poisson and negative binomial (NBD) expectations, as well as to ultrarelativistic quantum molecular dynamics (UrQMD) and hadron resonance gas (HRG) model predictions. Both NBD and Poisson baselines agree with data within the statistical and systematic uncertainties. UrQMD describes the measured net-ΛC1 and C3 at 200 GeV reasonably well but deviates from C2, and the deviation increases as a function of collision energy. The ratios of the measured cumulants show no features of critical fluctuations. The chemical freeze-out temperatures extracted from a recent HRG calculation, which was successfully used to describe the net-proton, net-kaon, and net-charge data, indicate Λ freeze-out conditions similar to those of kaons. However, large deviations are found when comparing with temperatures obtained from net-proton fluctuations. The net-Λ cumulants show a weak but finite dependence on the rapidity coverage in the acceptance of the detector, which can be attributed to quantum number conservation.
Keywords: dept.phy; peer-reviewed

Underlying event measurements in p+p collisions at s =200 GeV at RHIC - STAR Collaboration (Physical Review D, 2020)
Particle production sensitive to nonfactorizable and nonperturbative processes that contribute to the underlying event associated with a high transverse momentum (pT) jet in proton+proton collisions at √s=200 GeV is studied with the STAR detector. Each event is divided into three regions based on the azimuthal angle with respect to the highest-pT jet direction: in the leading jet direction (“Toward”), opposite to the leading jet (“Away”), and perpendicular to the leading jet (“Transverse”). In the Transverse region, the average charged particle density is found to be between 0.4 and 0.6 and the mean transverse momentum, ⟨pT⟩, between 0.5 and 0.7 GeV/c for particles with pT>0.2 GeV/c at mid-pseudorapidity (|η|<1) and jet pT>15 GeV/c. Both average particle density and ⟨pT⟩ depend weakly on the leading jet pT. Closer inspection of the Transverse region hints that contributions to the underlying event from initial- and final-state radiation are significantly smaller in these collisions than at the higher energies, up to 13 TeV, recorded at the LHC. Underlying event measurements associated with a high-pT jet will contribute to our understanding of QCD processes at hard and soft scales at RHIC energies, as well as provide constraints to modeling of underlying event dynamics.
Keywords: dept.phy; peer-reviewed

Bulk properties of the system formed in Au+Au collisions at sNN =14.5 GeV at the BNL STAR detector - STAR Collaboration (Physical Review C, 2020)
We report systematic measurements of bulk properties of the system created in Au+Au collisions at √sNN=14.5 GeV recorded by the STAR detector at the Relativistic Heavy Ion Collider (RHIC). The transverse momentum spectra of π±, K±, and p(¯p) are studied at midrapidity (|y|<0.1) for nine centrality intervals. The centrality, transverse momentum (pT), and pseudorapidity (η) dependence of inclusive charged particle elliptic flow (v2), and rapidity-odd charged particles directed flow (v1) results near midrapidity are also presented. These measurements are compared with the published results from Au+Au collisions at other energies, and from Pb+Pb collisions at √sNN=2.76 TeV. The results at √sNN=14.5 GeV show similar behavior as established at other energies and fit well in the energy dependence trend. These results are important as the 14.5-GeV energy fills the gap in μB, which is of the order of 100 MeV, between √sNN=11.5 and 19.6 GeV. Comparisons of the data with UrQMD and AMPT models show poor agreement in general.
Keywords: dept.phy; peer-reviewed

Measurement of groomed jet substructure observables in p+p collisions at s=200 GeV with STAR - STAR Collaboration (Physics Letters B, 2020)
In this letter, measurements of the shared momentum fraction (zg) and the groomed jet radius (Rg), as defined in the SoftDrop algorithm, are reported in p+p collisions at s=200 GeV collected by the STAR experiment. These substructure observables are differentially measured for jets of varying resolution parameters from R=0.2−0.6 in the transverse momentum range 15<pT,jet<60 GeV/c. These studies show that, in the pT,jet range accessible at s=200 GeV and with increasing jet resolution parameter and jet transverse momentum, the zg distribution asymptotically converges to the DGLAP splitting kernel for a quark radiating a gluon. The groomed jet radius measurements reflect a momentum-dependent narrowing of the jet structure for jets of a given resolution parameter, i.e., the larger the pT,jet, the narrower the first splitting. For the first time, these fully corrected measurements are compared to Monte Carlo generators with leading order QCD matrix elements and leading log in the parton shower, and to state-of-the-art theoretical calculations at next-to-leading-log accuracy. We observe that PYTHIA 6 with parameters tuned to reproduce RHIC measurements is able to quantitatively describe data, whereas PYTHIA 8 and HERWIG 7, tuned to reproduce LHC data, are unable to provide a simultaneous description of both zg and Rg, resulting in opportunities for fine parameter tuning of these models for p+p collisions at RHIC energies. We also find that the theoretical calculations without non-perturbative corrections are able to qualitatively describe the trend in data for jets of large resolution parameters at high pT,jet, but fail at small jet resolution parameters and low jet transverse momenta.
Keywords: Groomed jet radius; Jet substructure; SoftDrop; Splitting function; dept.phy; peer-reviewed

Investigation of the linear and mode-coupled flow harmonics in Au+Au collisions at sNN = 200 GeV - STAR Collaboration (Physics Letters B, 2020)
Flow harmonics (vn) of the Fourier expansion for the azimuthal distributions of hadrons are commonly employed to quantify the azimuthal anisotropy of particle production relative to the collision symmetry planes. While lower order Fourier coefficients (v2 and v3) are more directly related to the corresponding eccentricities of the initial state, the higher-order flow harmonics (vn>3) can be induced by a mode-coupled response to the lower-order anisotropies, in addition to a linear response to the same-order anisotropies. These higher-order flow harmonics and their linear and mode-coupled contributions can be used to more precisely constrain the initial conditions and the transport properties of the medium in theoretical models. The multiparticle azimuthal cumulant method is used to measure the linear and mode-coupled contributions in the higher-order anisotropic flow, the mode-coupled response coefficients, and the correlations of the event plane angles for charged particles as functions of centrality and transverse momentum in Au+Au collisions at nucleon-nucleon center-of-mass energy sNN= 200 GeV. The results are compared to similar LHC measurements as well as to several viscous hydrodynamic calculations with varying initial conditions.
Keywords: Collectivity; Correlation; Shear viscosity; dept.phy; peer-reviewed

Results on total and elastic cross sections in proton–proton collisions at s=200 GeV - STAR Collaboration (Physics Letters B, 2020)
We report results on the total and elastic cross sections in proton-proton collisions at s=200 GeV obtained with the Roman Pot setup of the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The elastic differential cross section was measured in the squared four-momentum transfer range 0.045≤−t≤0.135 GeV2. The value of the exponential slope parameter B of the elastic differential cross section dσ/dt∼e−Bt in the measured −t range was found to be B=14.32±0.09(stat.)−0.28+0.13(syst.) GeV−2. The total cross section σtot, obtained from extrapolation of the dσ/dt to the optical point at −t=0, is σtot=54.67±0.21(stat.)−1.38+1.28(syst.) mb. We also present the values of the elastic cross section σel=10.85±0.03(stat.)−0.41+0.49(syst.) mb, the elastic cross section integrated within the STAR t-range σeldet=4.05±0.01(stat.)−0.17+0.18(syst.) mb, and the inelastic cross section σinel=43.82±0.21(stat.)−1.44+1.37(syst.) mb. The results are compared with the world data.
Keywords: Diffraction; Elastic scattering; Proton-proton collisions; dept.phy; peer-reviewed

Identifying bound stellar companions to kepler exoplanet host stars using speckle imaging - Colton, Nicole M.; Horch, Elliott P; Everett, Mark E; Howell, Steve B; Davidson, James W., Jr.; Baptista, Brian J.; Casetti-Dinescu, Dana I (Astronomical Journal, 2021)
The Kepler mission and subsequent ground-based follow-up observations have revealed a number of exoplanet host stars with nearby stellar companions. This study presents speckle observations of 57 Kepler objects of interest (KOIs) that are also double stars, each observed over a 3-8 yr period, which has allowed us to track their relative motions with high precision. Measuring the position angle and separation of the companion with respect to the primary can help determine if the pair exhibits common proper motion, indicating it is likely to be a bound binary system. We report on the motions of 34 KOIs that have close stellar companions, three of which are triple stars, for a total of 37 companions studied. Eighteen of the 34 systems are confirmed exoplanet hosts, including one triple star, while four other systems have been subsequently judged to be false positives and twelve are yet to be confirmed as planet hosts. We find that 21 are most likely to be common proper motion pairs, 4 are line-of-sight companions, and 12 are of an uncertain disposition at present. The fraction of the confirmed exoplanet host systems that are common proper motion pairs is approximately 86% in this sample. In this subsample, the planets are exclusively found with periods of less than 110 days, so that in all cases the stellar companion is found at a much larger separation from the planet host star than the planet itself. A preliminary period-radius relation for the confirmed planets in our sample suggests no obvious differences at this stage with the full sample of known exoplanets. © 2020. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; peer-reviewed

HAT-P-68b: A transiting hot jupiter around a K5 dwarf star - Lindor, Bethlee M.; Hartman, Joel D.; Bakos, Gáspár Á.; Bhatti, Waqas; Csubry, Zoltan; Penev, Kaloyan; Bieryla, Allyson; Lathman, David W; Torres, Guillermo; Buchhave, Lars A; de Val-Borro, Miguel; Howard, Andrew W; et al. (Astronomical Journal, 2021)
We report the discovery by the ground-based Hungarian-made Automated Telescope Network (HATNet) survey of the transiting exoplanet HAT-P-68b, which has a mass of 0.724 ± 0.043 MJ, and radius of 1.072 ± 0.012 RJ. The planet is in a circular P = 2.2984 day orbit around a moderately bright V = 13.937 ± 0.030 magnitude K-dwarf star of mass ${0.673}_{-0.014}^{+0.020}$ M⊙, and radius 0.6726 ± 0.0069 R⊙. The planetary nature of this system is confirmed through follow-up transit photometry obtained with the Fred L. Whipple Observatory (FLWO) 1.2 m telescope, high-precision radial velocities measured using Keck I/High Resolution Echelle Spectrometer (HIRES), FLWO 1.5 m/Tillinghast Reflector Echelle Spectrograph (TRES), and Observatoire de Haute-Provence (OHP) 1.9 m/Sophie, and high-spatial-resolution speckle imaging from WIYN 3.5 m/DSSI. HAT-P-68 is at an ecliptic latitude of +3° and outside the field of view of both the NASA Transiting Exoplanet Survey Satellite primary mission and the K2 mission. The large transit depth of 0.036 mag (r band) makes HAT-P-68b a promising target for atmospheric characterization via transmission spectroscopy.
Keywords: dept.phy; peer-reviewed

Glioma tumors classified using visible resonance raman spectroscopy and machine learning - Wu, Binlin; Zhou, Yan; Zhang, Liang; Zhang, Shengjia; Yu, Xinguang; Wang, Eric; Zhu, Ke; Liu, Cheng-hui; Alfano, Robert R. (The Optical Society, 2020)
Machine learning algorithms were used to classify and analyze spectral data collected by visible resonance Raman spectroscopy to distinguish normal human brain tissue and glioma tumor tissues at different grades and show promising results. © OSA 2020 © 2020 The Author(s)
Keywords: dept.phy; ⛔ No DOI found

Measurement of away-side broadening with self-subtraction of flow in Au+Au collisions at √sNN = 200 GeV - STAR Collaboration (Chinese Physics C, 2020)
High transverse momentum ( ) particle production is suppressed owing to the parton (jet) energy loss in the hot dense medium created in relativistic heavy-ion collisions. Redistribution of energy at low-to-modest has been difficult to measure, owing to large anisotropic backgrounds. We report a data-driven method for background evaluation and subtraction, exploiting the away-side pseudorapidity gaps, to measure the jetlike correlation shape in Au+Au collisions at GeV in the STAR experiment. The correlation shapes, for trigger particles and various associated particle ranges within , are consistent with Gaussians, and their widths increase with centrality. The results indicate jet broadening in the medium created in central heavy-ion collisions.
Keywords: dept.phy; di-hadron correlations; heavy-ion; jet; peer-reviewed

Measurement of the central exclusive production of charged particle pairs in proton-proton collisions at √s = 200 GeV with the STAR detector at RHIC - STAR Collaboration (Journal of High Energy Physics, 2020)
We report on the measurement of the Central Exclusive Production of charged particle pairs h+h− (h = π, K, p) with the STAR detector at RHIC in proton-proton collisions at s$$ \sqrt{s} $$= 200 GeV. The charged particle pairs produced in the reaction pp → p′ + h+h− + p′ are reconstructed from the tracks in the central detector and identified using the specific energy loss and the time of flight method, while the forward-scattered protons are measured in the Roman Pot system. Exclusivity of the event is guaranteed by requiring the transverse momentum balance of all four final-state particles. Differential cross sections are measured as functions of observables related to the central hadronic final state and to the forward-scattered protons. They are measured in a fiducial region corresponding to the acceptance of the STAR detector and determined by the central particles’ transverse momenta and pseudorapidities as well as by the forward-scattered protons’ momenta. This fiducial region roughly corresponds to the square of the four-momentum transfers at the proton vertices in the range 0.04 GeV2 < −t1, −t2 < 0.2 GeV2, invariant masses of the charged particle pairs up to a few GeV and pseudorapidities of the centrally-produced hadrons in the range |η| < 0.7. The measured cross sections are compared to phenomenological predictions based on the Double Pomeron Exchange (DPE) model. Structures observed in the mass spectra of π+π− and K+K− pairs are consistent with the DPE model, while angular distributions of pions suggest a dominant spin-0 contribution to π+π− production. For π+π− production, the fiducial cross section is extrapolated to the Lorentz-invariant region, which allows decomposition of the invariant mass spectrum into continuum and resonant contributions. The extrapolated cross section is well described by the continuum production and at least three resonances, the f0(980), f2(1270) and f0(1500), with a possible small contribution from the f0(1370). Fits to the extrapolated differential cross section as a function of t1 and t2 enable extraction of the exponential slope parameters in several bins of the invariant mass of π+π− pairs. These parameters are sensitive to the size of the interaction region.
Keywords: Diffraction; Forward physics; Hadron-Hadron scattering (experiments); dept.phy; peer-reviewed

Measurement of D0 -meson + hadron two-dimensional angular correlations in Au+ Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2020)
Open heavy-flavor hadrons provide unique probes of the medium produced in ultrarelativistic heavy-ion collisions. Due to their increased mass relative to light-flavor hadrons, long lifetime, and early production in hard-scattering interactions, they provide access to the full evolution of the partonic medium formed in heavy-ion collisions. This paper reports two-dimensional (2D) angular correlations between neutral D mesons and unidentified charged particles produced in minimum-bias Au+Au collisions at √sNN=200GeV. D0 and ¯¯¯D0 mesons are reconstructed via their weak decay to K∓π± using the Heavy Flavor Tracker in the Solenoidal Tracker at RHIC experiment. Correlations on relative pseudorapidity and azimuth (Δη,Δϕ) are presented for peripheral, midcentral, and central collisions with D0 transverse momentum from 2–10GeV/c. Attention is focused on the 2D peaked correlation structure near the triggered D0 meson, the near-side (NS) peak, which serves as a proxy for a charm-quark-containing jet. The correlated NS yield of charged particles per D0 meson and the 2D widths of the NS peak increase significantly from peripheral to central collisions. These results are compared with similar correlations using unidentified charged particles, consisting primarily of light-flavor hadrons, at similar trigger particle momenta. Similar per-trigger yields and widths of the NS correlation peak are observed. The present results provide additional evidence that D0 mesons undergo significant interactions with the medium formed in heavy-ion collision and show, for the first time, significant centrality evolution of the NS 2D peak in the correlations of particles associated with a heavy-flavor hadron produced in these collisions.
Keywords: dept.phy; peer-reviewed

First measurement of λc baryon production in au+au collisions at sNN=200 GeV - STAR Collaboration (Physical Review Letters, 2020)
We report on the first measurement of the charmed baryon Λ±c production at midrapidity (|y|<1) in Au+Au collisions at √sNN=200 GeV collected by the STAR experiment at the Relativistic Heavy Ion Collider. The Λc/D0 [denoting (Λ+c+Λ−c)/(D0+¯D0)] yield ratio is measured to be 1.08±0.16 (stat)±0.26 (sys) in the 0%–20% most central Au+Au collisions for the transverse momentum (pT) range 3<pT<6 GeV/c. This is significantly larger than the pythia model calculations for p+p collisions. The measured Λc/D0 ratio, as a function of pT and collision centrality, is comparable to the baryon-to-meson ratios for light and strange hadrons in Au+Au collisions. Model calculations including coalescence hadronization for charmed baryon and meson formation reproduce the features of our measured Λc/D0 ratio.
Keywords: Au+Au collisions; Bosons; Colliding beam accelerators; Germanium compounds; Gold compounds; Hadronization; Hadrons; Heavy ions; Mid-rapidity; Model calculations; Particle detectors; Relativistic Heavy Ion Collider; STAR experiment; Transverse momenta; Yield ratios; dept.phy; peer-reviewed

Speckle interferometry at SOAR in 2019 - Tokovinin, Andrei; Mason, Brian D.; Mendez, Rene A.; Costa, Edgardo; Horch, Elliott P. (The Astronomical Journal, 2020)
The results of speckle-interferometric observations at the 4.1 m Southern Astrophysical Research Telescope in 2019 are given, totaling 2555 measurements of 1972 resolved pairs with separations from 15 mas (median 0.″21) and magnitude difference up to 6 mag, and non-resolutions of 684 targets. We resolved for the first time 90 new pairs or subsystems in known binaries. This work continues our long-term speckle program. Its main goal is to monitor orbital motion of close binaries, including members of high-order hierarchies and Hipparcos pairs in the solar neighborhood. We give a list of 127 orbits computed using our latest measurements. Their quality varies from excellent (25 orbits of grades 1 and 2) to provisional (47 orbits of grades 4 and 5). © 2020 The American Astronomical Society. All rights reserved.
Keywords: 1081; 154; 1777; Astrophysics - Solar and Stellar Astrophysics; Binary stars; Multiple stars; Visual binary stars; dept.phy; peer-reviewed

Observations of binary stars with the differential speckle survey instrument. IX. Observations of known and suspected binaries, and a partial survey of be stars - Horch, Elliott P.; van Belle, Gerard T.; Davidson, James W., Jr.; Willmarth, Daryl; Fekel, Francis C.; Muterspaugh, Matthew; Casetti-Dinescu, Dana I.; Hahne, Frederick W.; Granucci, Nicole M.; Clark, Catherine; Winters, Jennifer G.; Rupert, Justin D.; et al. (The Astronomical Journal, 2020)
We report 370 measures of 170 components of binary and multiple-star systems, obtained from speckle imaging observations made with the Differential Speckle Survey Instrument at Lowell Observatory's Discovery Channel Telescope in 2015 through 2017. Of the systems studied, 147 are binary stars, 10 are seen as triple systems, and 1 quadruple system is measured. Seventy-six high-quality nondetections and 15 newly resolved components are presented in our observations. The uncertainty in relative astrometry appears to be similar to our previous work at Lowell, namely, linear measurement uncertainties of approximately 2 mas, and the relative photometry appears to be uncertain at the 0.1-0.15 mag level. Using these measures and those in the literature, we calculate six new visual orbits, including one for the Be star 66 Oph and two combined spectroscopic-visual orbits. The latter two orbits, which are for HD 22451 (YSC 127) and HD 185501 (YSC 135), yield individual masses of the components at the level of 2% or better, and independent distance measures that in one case agrees with the value found in the Gaia DR2 and in the other disagrees at the 2σ level. We find that HD 22451 consists of an F6V+F7V pair with orbital period of 2401.1 ± 3.2 days and masses of 1.342 ± 0.029 and 1.236 ± 0.026M⊙. For HD 185501, both stars are G5 dwarfs that orbit one another with a period of 433.94 ± 0.15 days, and the masses are 0.898 ± 0.012 and 0.876 ± 0.012M⊙ . We discuss the details of both the new discoveries and the orbit objects. © 2020. The American Astronomical Society. All rights reserved..
Keywords: Astrophysics - Earth and Planetary Astrophysics; Astrophysics - Instrumentation and Methods for Astrophysics; Astrophysics - Solar and Stellar Astrophysics; dept.phy; peer-reviewed

A hot terrestrial planet orbiting the bright M dwarf L 168-9 unveiled by TESS - Astudillo-Defru, N.; Cloutier, R.; Wang, S. X.; Teske, J.; Brahm, R.; Hellier, C.; Ricker, G.; Vand erspek, R.; Latham, D.; Seager, S.; Winn, J. N.; Jenkins, J. M.; et al. (Astronomy & Astrophysics, 2020)
We report the detection of a transiting super-Earth-sized planet (R = 1.39 ± 0.09 R⊕ ) in a 1.4-day orbit around L 168-9 (TOI-134), a bright M1V dwarf (V = 11, K = 7.1) located at 25.15 ± 0.02 pc. The host star was observed in the first sector of the Transiting Exoplanet Survey Satellite (TESS) mission. For confirmation and planet mass measurement purposes, this was followed up with ground-based photometry, seeing-limited and high-resolution imaging, and precise radial velocity (PRV) observations using the HARPS and Magellan/PFS spectrographs. By combining the TESS data and PRV observations, we find the mass of L 168-9 b to be 4.60 ± 0.56 M⊕ and thus the bulk density to be 1.74-0.33+0.44 times higher than that of the Earth. The orbital eccentricity is smaller than 0.21 (95% confidence). This planet is a level one candidate for the TESS mission's scientific objective of measuring the masses of 50 small planets, and it is one of the most observationally accessible terrestrial planets for future atmospheric characterization. © ESO 2020.
Keywords: Astrophysics - Earth and Planetary Astrophysics; Astrophysics - Solar and Stellar Astrophysics; Atmospheric characterization; Earth (planet); High-resolution imaging; Mass measurements; Orbital eccentricity; Orbits; Planetary systems; Planets; Radial velocity; Scientific objectives; Seeing limited; Stars: individual: L 168-9; Stars: late-type; Techniques: photometric; Techniques: radial velocities; Terrestrial planets; dept.phy; peer-reviewed; planetary systems; stars: individual: L 168-9; stars: late-type; techniques: photometric; techniques: radial velocities

Distinguishing metastatic triple-negative breast cancer from nonmetastatic breast cancer using second harmonic generation imaging and resonance Raman spectroscopy - Bendau, Ethan; Smith, Jason; Zhang, Lin; Ackerstaff, Ellen; Kruchevsky, Natalia; Wu, Binlin; Koutcher, Jason A.; Alfano, Robert; Shi, Lingyan (Journal of Biophotonics, 2020)
Triple-negative breast cancer (TNBC) is an aggressive subset of breast cancer that is more common in African-American and Hispanic women. Early detection followed by intensive treatment is critical to improving poor survival rates. The current standard to diagnose TNBC from histopathology of biopsy samples is invasive and time-consuming. Imaging methods such as mammography and magnetic resonance (MR) imaging, while covering the entire breast, lack the spatial resolution and specificity to capture the molecular features that identify TNBC. Two nonlinear optical modalities of second harmonic generation (SHG) imaging of collagen, and resonance Raman spectroscopy (RRS) potentially offer novel rapid, label-free detection of molecular and morphological features that characterize cancerous breast tissue at subcellular resolution. In this study, we first applied MR methods to measure the whole-tumor characteristics of metastatic TNBC (4T1) and nonmetastatic estrogen receptor positive breast cancer (67NR) models, including tumor lactate concentration and vascularity. Subsequently, we employed for the first time in vivo SHG imaging of collagen and ex vivo RRS of biomolecules to detect different microenvironmental features of these two tumor models. We achieved high sensitivity and accuracy for discrimination between these two cancer types by quantitative morphometric analysis and nonnegative matrix factorization along with support vector machine. Our study proposes a new method to combine SHG and RRS together as a promising novel photonic and optical method for early detection of TNBC.
Keywords: Breast; Breast Neoplasms; Collagen; Diseases; Factorization; Feature extraction; Female; Harmonic generation; Humans; Label-free detection; Lactate concentration; Magnetic resonance; Mammography; Matrix algebra; Molecular imaging; Morphological features; Morphometric analysis; Nonlinear optics; Nonnegative matrix factorization; Raman spectrometry; Raman spectroscopy; Resonance Raman spectroscopy; Second Harmonic Generation Microscopy; Spectrum Analysis, Raman; Subcellular resolution; Support vector machines; Triple Negative Breast Neoplasms; Triple-negative breast cancers; Tumors; breast; breast tumor; dept.phy; diagnostic imaging; female; human; mammography; peer-reviewed; second harmonic generation microscopy; triple negative breast cancer

Synthesis and characterization of CuS, CuS/graphene oxide nanocomposite for supercapacitor applications - Singhal, Rahul; Thorne, David; LeMaire, Peter K.; Martinez, Xavier; Zhao, Chen; Gupta, Ram K.; Uhl, David; Scanley, Ellen; Broadbridge, Christine C.; Sharma, Rakesh K. (AIP Advances, 2020)
Supercapacitors or electrochemical capacitors are receiving greater interest because of their high-power density, long life, and low maintenance. We have synthesized CuS nanoparticles and graphene oxide (CuS-GO) nanocomposites for supercapacitor applications because of their low cost and excellent electrochemical properties. The phase purity of each material was determined using powder XRD studies. The bandgap was determined by UV-visible spectrophotometric studies. Scanning electron microscope and transmission electron microscope images revealed the nano-scale morphology of the synthesized particles. All the electrochemical measurements were conducted in a standard three-electrode configuration, using a platinum wire as the counter electrode and Hg/HgO as the reference electrode. CuS and its composites with graphene oxide on nickel foam were used as working electrodes. All the electrochemical measurements were performed in 3M KOH solution. The CuS-GO nanocomposite electrode showed a specific capacitance of 250 F/g, 225 F/g, 182 F/g, 166 F/g, 161 F/g, and 158 F/g at a current density of 0.5 A/g, 1 A/g, 5 A/g, 10 A/g, 15 A/g, and 20 A/g, respectively. CuS-GO electrodes showed a specific capacitance retention of 70% after 5000 charge-discharge cycles at a current density of 5 A/g. © 2020 Author(s).
Keywords: Capacitance; Charge-discharge cycle; Copper compounds; Electric discharges; Electrochemical capacitor; Electrochemical electrodes; Electrochemical measurements; Foams; Graphene; Mercury compounds; Nanocomposite electrodes; Nanocomposites; Potassium hydroxide; Scanning electron microscopy; Spectrophotometric study; Supercapacitor; Supercapacitor application; Synthesis (chemical); Synthesis and characterizations; Transmission electron; Transmission electron microscopy; dept.phy; peer-reviewed

Local RR Lyrae stars: native and alien - Zinn, R; Chen, X; Layden, A C; Casetti-Dinescu, D I (Monthly Notices of the Royal Astronomical Society, 2020)
Measurements of [Fe/H] and radial velocity are presented for 89 RR Lyrae (RRL) candidates within 6 kpc of the Sun. After the removal of two suspected non-RRLs, these stars were added to an existing data base, which yielded 464 RRLs with [Fe/H] on a homogeneous scale. Using data from the Gaia satellite (Data Release 2), we calculated the positions and space velocities for this sample. These data confirm the existence of a thin disc of RRL with [α/Fe] ∼ solar. The majority of the halo RRLs with large total energies have near-zero angular momenta about the Z-axis. Kinematically, these stars closely resemble the Gaia-Sausage/Gaia-Enceladus stars that others have proposed are debris from the merger of a large galaxy with the Milky Way. The metallicity and period distributions of the RRLs and their positions in the period-amplitude diagram suggest that this disrupted galaxy was as massive as the Large Magellanic Cloud and possibly greater. © 2019 The Author(s)
Keywords: Dynamics; Galaxy: formation; Galaxy: kinematics; Stars: variables: RR Lyrae; dept.phy; peer-reviewed